Polyester film for semiconductor manufacturing process

CN122953802APending Publication Date: 2026-10-20MITSUBISHI CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202580021228.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-28
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

[0064]根据本发明,可以提供一种半导体制造工序用聚酯薄膜,其可回收性良好,同时应力松弛性、尤其应力松弛性和机械强度优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention is a polyester film for semiconductor manufacturing processes. The polyester film has a thermoplastic polyester layer comprising thermoplastic polyester, the thermoplastic polyester layer being the surface layer (A) of the polyester film. The surface layer (A) has a hardness of less than 450 MPa as measured by a nanoindenter at 23±5°C, and the Young's modulus of the polyester film is greater than 2 GPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polyester film for semiconductor manufacturing processes and its application method. Background Technology

[0002] Semiconductor devices are typically manufactured by forming electronic circuits on the surface of semiconductor wafers, such as silicon wafers, then using a dicing process to monolithically produce semiconductor chips, and finally packaging these monolithic semiconductor chips. The dicing process is typically blade cutting, while laser-based stealth dicing is becoming increasingly practical. Furthermore, to achieve thinner chips, the back side of the semiconductor wafer is usually ground to adjust its thickness.

[0003] In recent years, a process known as pre-dicing has been used to further reduce the thickness of semiconductor chips. Pre-dicing involves using a dicing blade to form grooves of a specified depth on the surface of a wafer, followed by grinding from the back side of the wafer to monolithize the wafer into a chip. Additionally, a pre-dicing method utilizing stealth dicing, known as stealth dicing before grinding, has also been researched in recent years.

[0004] When semiconductor wafers are back-side ground, a dicing tape made of adhesive tape is usually attached to the surface side of the wafer to protect the electronic circuitry. It is known that the substrate of the dicing tape is obtained by laminating a soft layer such as a polyethylene layer on a support material such as a polyester film as a surface layer to relax the shearing force acting on the wafer and the monolithized chip during wafer grinding (see, for example, Patent Document 1).

[0005] In addition to the above, various other thin films have been known in the past as thin films used in semiconductor manufacturing processes. For example, Patent Document 2 discloses a surface protection film having an anchoring coating comprising a copolymer polyurethane resin on one side of the core material film. Patent Documents 3 and 4 disclose three-layer films as substrate films for back-side grinding tapes: a surface back layer and an intermediate layer formed of a soft polyester and a polyester-based elastomer, respectively; and a three-layer film with a surface back layer formed of a polyester resin and an intermediate layer formed of a soft polyester resin. Furthermore, Patent Document 5 discloses a carrier tape in which the intermediate layer is formed of a copolymer polyester and the two surface layers are formed of polybutylene terephthalate or polybutylene naphthalate.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2023-94525

[0009] Patent Document 2: Japanese Patent Application Publication No. 2012-216619

[0010] Patent Document 3: Japanese Patent Application Publication No. 2010-225675

[0011] Patent Document 4: Japanese Patent Application Publication No. 2021-146675

[0012] Patent Document 5: Japanese Patent Application Publication No. 04-257444 Summary of the Invention

[0013] The problem that the invention aims to solve

[0014] However, polyester resin is widely used and can be recycled both physically and chemically based on depolymerization reactions, making it a highly recyclable resin. Therefore, its reuse is being promoted for the large quantities of PET bottles consumed. Furthermore, in recent years, from an environmental protection perspective, the reuse of polyester used in various applications is required not only for PET bottles, but also for other types of polyester. For example, the reuse of substrates is also required for engineering films such as dicing tapes used in semiconductor manufacturing processes.

[0015] However, while existing polyester films offer excellent recyclability, their monomers cannot adequately relax stress or sufficiently improve mechanical strength, making them unsuitable for practical use in semiconductor manufacturing processes. For example, the polyester films disclosed in Patent Documents 3-5 struggle to achieve excellent stress relaxation properties while simultaneously improving mechanical strength.

[0016] On the other hand, as in Patent Documents 1 and 2, when different types of resin layers, such as polyethylene layers, are laminated on a substrate formed of PET, although the stress relaxation properties are excellent, there is a problem of difficulty in recycling.

[0017] Furthermore, when recycling the core film disclosed in Patent Document 2, it is difficult to use it as a recycled material if the anchoring coating containing copolymer polyurethane resin coated on the core film is not cleaned and removed using a cleaning agent or the like.

[0018] Therefore, the objective of this invention is to provide a polyester film for semiconductor manufacturing processes that has good recyclability and excellent stress relaxation properties, especially stress relaxation properties and mechanical strength.

[0019] Solution for solving the problem

[0020] The present invention provides the following [1] to

[22] .

[0021] [1] A polyester film for semiconductor manufacturing processes, the polyester film having a thermoplastic polyester layer comprising a thermoplastic polyester.

[0022] The thermoplastic polyester layer is the surface layer (A) of the polyester film.

[0023] The surface layer (A) has a hardness of less than 450 MPa as measured by a nanoindenter at 23±5℃.

[0024] The polyester film has a Young's modulus of 2 GPa or higher.

[0025] [2] A polyester film for semiconductor manufacturing process, wherein the hardness of one surface of the film is less than 450 MPa as measured by a nanoindenter at 23±5°C.

[0026] [3] The polyester film for semiconductor manufacturing process according to [1] or [2] above, wherein the polyester film has a hardness gradient that increases from one surface of the film toward the center in the thickness direction of the film.

[0027] [4] A polyester film for semiconductor manufacturing processes, comprising a copolyester formed from a copolymer of a dicarboxylic acid component and a diol component.

[0028] Let (A1) be the proportion (molar percentage) of dicarboxylic acid components with 4 to 10 carbon atoms (excluding terephthalic acid) in all polyester components contained on one surface of the film.

[0029] Let (A4) be the percentage (molar percentage) of diols other than ethylene glycol in the total polyester content of the surface.

[0030] Let (B1) be the percentage (molar percentage) of dicarboxylic acid components (excluding terephthalic acid) with 4 to 10 carbon atoms in all polyester components contained in the center part of the film thickness direction.

[0031] When the percentage (molar percentage) of diols other than ethylene glycol in the total polyester content at the center of the film thickness direction is set as (B4),

[0032] (A1) + (A4) is higher than (B1) + (B4).

[0033] [5] A polyester film for semiconductor manufacturing process according to any one of [1] to [4] above, wherein the polyester film comprises a copolyester (a), the copolyester (a) being a copolymer comprising a dicarboxylic acid component comprising terephthalic acid and a diol component comprising an aliphatic diol (Y).

[0034] [6] The polyester film for semiconductor manufacturing process according to [5] above, wherein the copolyester (a) comprises a copolyester (a1), wherein the copolyester (a1) is a copolymer of a dicarboxylic acid component (X2) comprising terephthalic acid and a dicarboxylic acid component (X2) having 4 to 10 carbon atoms, and a diol component comprising an aliphatic diol (Y).

[0035] [7] The polyester film for semiconductor manufacturing process according to [5] or [6] above, wherein the copolyester (a) comprises a copolyester (a1-1), which is a copolymer of a dicarboxylic acid component comprising terephthalic acid (X1) and a dicarboxylic acid component comprising 4 to 10 carbon atoms (X2), and a diol component comprising an aliphatic diol (Y2) comprising 4 to 8 carbon atoms.

[0036] [8] A polyester film for semiconductor manufacturing process according to any one of [1] to [7] above, wherein the polyester film is a multilayer film having the surface layer (A) and the intermediate layer (B).

[0037] [9] A polyester film for semiconductor manufacturing process according to any one of [1], [3] and [5] to [8] above, wherein the surface layer (A) comprises a copolyester formed of a copolymer of a dicarboxylic acid component and a diol component.

[0038] Let (A1) be the proportion (molar percentage) of dicarboxylic acid components with 4 to 10 carbon atoms (excluding terephthalic acid) in all polyester components of the surface layer (A).

[0039] When the proportion (molar%) of diol components other than ethylene glycol in the total polyester content of the surface layer (A) is set as (A4),

[0040] (A1) + (A4) is 5 mol% or more.

[0041]

[10] The polyester film for semiconductor manufacturing process according to [8] or [9] above, wherein the intermediate layer (B) comprises a copolyester formed from a copolymer of a dicarboxylic acid component and a diol component.

[0042] Let (B1) be the percentage (molar percentage) of dicarboxylic acid components (excluding terephthalic acid) with 4 to 10 carbon atoms in all the polyester contained in the intermediate layer (B), and...

[0043] When the proportion (molar percentage) of diols other than ethylene glycol in the total polyester content of the intermediate layer (B) is set as (B4),

[0044] (B1) + (B4) is less than 30 mol%.

[0045]

[11] A polyester film for semiconductor manufacturing process according to any one of [8] to

[10] above, wherein the surface layer (A) comprises a copolyester formed from a copolymer of a dicarboxylic acid component and a diol component.

[0046] The intermediate layer (B) comprises a copolyester formed from a copolymer of dicarboxylic acid components and diol components.

[0047] Let (A1) be the proportion (molar percentage) of dicarboxylic acid components with 4 to 10 carbon atoms (excluding terephthalic acid) in all polyester components of the surface layer (A).

[0048] Let (A4) be the percentage (molar percentage) of diol components other than ethylene glycol in the total polyester content of the surface layer (A).

[0049] Let (B1) be the percentage (molar percentage) of dicarboxylic acid components (excluding terephthalic acid) with 4 to 10 carbon atoms in all the polyester contained in the intermediate layer (B), and...

[0050] When the proportion (molar percentage) of diols other than ethylene glycol in the total polyester content of the intermediate layer (B) is set as (B4),

[0051] (A1) + (A4) is higher than (B1) + (B4), and the difference is greater than 5 mol%.

[0052]

[12] A polyester film for semiconductor manufacturing process according to any one of [1], [3] and [5] to

[11] above, wherein the surface layer (A) contains an impact resistance modifier.

[0053]

[13] The polyester film for semiconductor manufacturing process according to

[12] above, wherein the content of the impact resistance modifier is less than 30% by mass in the surface layer (A).

[0054]

[14] The polyester film for semiconductor manufacturing process according to

[12] or

[13] above, wherein the content of the impact resistance modifier is less than 15% by mass in the polyester film.

[0055]

[15] A polyester film for semiconductor manufacturing process according to any one of [1] to

[14] above, wherein the polyester film is a stretched film.

[0056]

[16] A polyester film for semiconductor manufacturing process according to any one of [1] to

[15] above, wherein the polyester film is a co-extruded stretched film.

[0057]

[17] A polyester film for semiconductor manufacturing process according to any one of [1] to

[16] above, wherein the polyester film is for back-side grinding or cutting.

[0058]

[18] A laminated thin film comprising: a polyester film for semiconductor manufacturing process as described in any one of [1] to

[17] above, and at least one resin layer disposed on one or the other surface of the polyester film for semiconductor manufacturing process.

[0059]

[19] According to the laminated film described in

[18] above, wherein the resin layer includes an antistatic layer, and the surface resistivity of one side of the antistatic layer is 1×10⁻⁶. 12 Below Ω / □.

[0060]

[20] The laminated film according to

[18] or

[19] above, wherein the resin layer comprises an adhesive layer.

[0061]

[21] The laminated film according to any one of

[18] to

[20] above, wherein an easy-to-adhere layer is provided on one surface and an antistatic layer is provided on the other surface.

[0062]

[22] A method of use in which the polyester film used in the semiconductor manufacturing process described in any one of [1] to

[17] above, or the laminated film described in any one of

[18] to

[21] above, is used for back-side grinding or cutting.

[0063] Invention Effects

[0064] According to the present invention, a polyester film for semiconductor manufacturing processes can be provided, which has good recyclability and excellent stress relaxation properties, especially stress relaxation and mechanical strength. Detailed Implementation

[0065] The embodiments of the present invention will now be described in detail. However, the present invention is not limited to the embodiments described below, and can be implemented in any way without departing from the spirit of the present invention.

[0066] <Hardness>

[0067] In one embodiment of the polyester film for semiconductor manufacturing processes of the present invention (hereinafter, sometimes simply referred to as "the film"), the hardness (hereinafter, sometimes simply referred to as "hardness") of one surface of the film, measured by a nanoindenter at 23±5°C, is 450 MPa or less.

[0068] This film is a polyester film having a thermoplastic polyester layer comprising a thermoplastic polyester layer, which is the surface layer (A) of this film. The surface layer (A) is the layer constituting the surface of this film. As described above, the hardness of one surface of this film is 450 MPa or less; therefore, the hardness of the surface layer (A) measured by a nanoindenter at 23 ± 5 °C is 450 MPa or less.

[0069] By using a polyester film, this film exhibits excellent recyclability. Furthermore, by setting the hardness of one surface (i.e., the hardness of surface layer (A)) to below 450 MPa, it demonstrates good stress relaxation characteristics. Therefore, by attaching a protective sheet based on this film to a semiconductor wafer, it is possible to properly protect the wafer and chip during semiconductor manufacturing processes. More specifically, it can appropriately relax stresses such as shear forces acting on the wafer and chip during wafer grinding, effectively preventing wafer and chip breakage.

[0070] From the viewpoint of further improving stress relaxation characteristics, the aforementioned hardness is preferably 350 MPa or less, more preferably 310 MPa or less, even more preferably 250 MPa or less, even more preferably 200 MPa or less, and still more preferably 180 MPa or less. The hardness of this film is not particularly limited, but is preferably 40 MPa or more, more preferably 60 MPa or more, even more preferably 80 MPa or more, and even more preferably 100 MPa or more. This film imparts stiffness by increasing the mechanical strength, such as Young's modulus, of the film by making the hardness of one surface (i.e., the surface layer (A)) a certain level or higher, thus enabling proper wafer support when attached as a protective sheet.

[0071] This film requires only that the hardness of at least one surface be within the aforementioned range, but it is preferable that the hardness of both surfaces be within the aforementioned range. Wafers with protective films attached are sometimes placed on an adsorption stage during grinding, with the protective film in between. In this case, the adsorption stage is in contact with the side opposite to the side bonded to the wafer. Therefore, when the hardness of both surfaces is below the specified value as described above, stress can be relaxed on one surface while simultaneously filling in the unevenness caused by foreign matter on the adsorption stage on the other surface, while maintaining a tight seal with the adsorption stage. As a result, cracks in the wafer or chip caused by foreign matter can be further reduced.

[0072] The hardness of this film can be adjusted by the type of resin used in the film, the composition of each resin, and the amount of each resin. Furthermore, it can be adjusted by various manufacturing conditions in the film manufacturing method, such as by the heat-setting temperature. More specifically, if the heat-setting temperature is increased, the crystals contained in the film become more easily melted during heat setting, thereby making it easier to reduce the hardness.

[0073] It should be noted that the surface hardness of polyester film (the hardness of the surface layer (A)) should preferably be determined by pressing a probe of a nanoindenter into the surface of the polyester film. However, even when there is a resin layer on the surface of the polyester film, if the thickness of the resin layer is less than several hundred nm (e.g., less than 500 nm), the surface hardness of the polyester film (the surface layer (A)) can also be determined by pressing a probe into the surface of the resin layer.

[0074] Young's Modulus

[0075] The Young's modulus of this film is preferably 2 GPa or higher. When the Young's modulus is 2 GPa or higher, the mechanical strength is good, allowing the film to properly hold wafers and chips, and easily preventing damage to wafers and chips during semiconductor manufacturing processes. Therefore, this film can be appropriately used in semiconductor manufacturing. The Young's modulus is further preferably 3 GPa or higher, and even more preferably 3.5 GPa or higher. From the viewpoint of ensuring the flexibility of this film and reducing hardness, the Young's modulus is preferably 20 GPa or lower, more preferably 15 GPa or lower, even more preferably 10 GPa or lower, and even more preferably 5 GPa or lower. Details of the method for measuring the Young's modulus are as described in the examples. It should be noted that the Young's modulus is preferably measured along the length (MD) and width (TD) directions of the film, and their average value is obtained. It should be noted that on one or both surfaces of the polyester film, there may be resin layers such as easy-to-adhere layers or antistatic layers. If the thickness of the resin layer is less than several hundred nm (e.g., less than 500 nm), the influence of the resin layer can be substantially ignored in the measurement of the Young's modulus. Therefore, the Young's modulus of a polyester film having such a resin layer on its surface can be measured and used as the Young's modulus of the polyester film. The same applies to the various physical properties of the polyester film described later.

[0076] In addition, Young's modulus can be appropriately controlled by the layer composition of the film, the thickness of each layer, the type and amount of resin used in each layer, and the manufacturing method.

[0077] [Thermoplastic polyester layer]

[0078] As described above, the thermoplastic polyester layer constituting the surface layer (A) of this film contains thermoplastic polyester. The thermoplastic polyester layer only needs to contain at least thermoplastic polyester. By including thermoplastic polyester in the surface layer (A), this film achieves excellent stress relaxation properties while ensuring recyclability and mechanical strength.

[0079] [Copolyester (a)]

[0080] This film contains a copolyester formed from a copolymer of dicarboxylic acid and diol components. By containing the copolyester, this film easily reduces hardness and improves stress relaxation properties.

[0081] As a copolyester, specifically, copolyester (a) can be cited as an example, which is a copolymer of a dicarboxylic acid component containing terephthalic acid (X1) and a diol component containing an aliphatic diol (Y). Copolyester (a) is a substance other than the polyarylate (c) described later. The copolyester (a) contained in this film preferably has thermoplastic properties.

[0082] (Copolyester (a1))

[0083] As the copolyester (a), a preferred example is a copolyester (a1), which is a copolymer of a dicarboxylic acid component comprising terephthalic acid (X1) and a dicarboxylic acid component comprising 4 to 10 carbon atoms (X2), and a diol component comprising an aliphatic diol (Y). The dicarboxylic acid component comprising 4 to 10 carbon atoms (X2) refers to a dicarboxylic acid component comprising 4 to 10 carbon atoms other than terephthalic acid (X1).

[0084] The copolyester (a1) is a condensation polymer containing terephthalic acid (X1) and a dicarboxylic acid component with 4 to 10 carbon atoms (X2), and a diol component containing an aliphatic diol (Y). By using a dicarboxylic acid component with 4 to 10 carbon atoms (X2) other than terephthalic acid as the dicarboxylic acid, it is easy to reduce hardness and improve stress relaxation properties.

[0085] Examples of dicarboxylic acid components (X2) with 4 to 10 carbon atoms include aromatic dicarboxylic acids, alicyclic dicarboxylic acids, aliphatic dicarboxylic acids, and polyfunctional acids. Among these, aromatic dicarboxylic acids and aliphatic dicarboxylic acids are preferred, and from the viewpoint of easily reducing hardness, aliphatic dicarboxylic acids are preferred. Aliphatic dicarboxylic acids can be used alone as a dicarboxylic acid component (X2) with 4 to 10 carbon atoms, or they can be used in combination with two or more dicarboxylic acid components with 4 to 10 carbon atoms.

[0086] Examples of aliphatic dicarboxylic acids with 4 to 10 carbon atoms include succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, and sebacic acid, among which adipic acid and sebacic acid are more preferred from the viewpoint of ease of polymerization, and adipic acid is even more preferred. Furthermore, isophthalic acid is preferred as an aromatic dicarboxylic acid.

[0087] The proportion of the dicarboxylic acid component (X2) with 4 to 10 carbon atoms in the dicarboxylic acid component constituting the copolyester (a1) is not particularly limited, for example, it is 5 mol% or more and 35 mol% or less, preferably 7 mol% or more and 30 mol% or less, more preferably 9 mol% or more and 25 mol% or less, and even more preferably 11 mol% or more and 20 mol% or less.

[0088] In addition, the proportion of terephthalic acid (X1) in the dicarboxylic acid component constituting the copolyester (a1) is, for example, 65 mol% or more and 95 mol% or less, preferably 75 mol% or more and 92 mol% or less, and more preferably 80 mol% or more and 90 mol% or less.

[0089] Furthermore, in the copolyester (a1), the dicarboxylic acid component can be formed from terephthalic acid (X1) and a dicarboxylic acid component with 4 to 10 carbon atoms (X2). Without prejudice to the spirit of the invention, other dicarboxylic acid components (other dicarboxylic acid components (X3)) besides terephthalic acid (X1) and the dicarboxylic acid component with 4 to 10 carbon atoms (X2) can also be included as copolymer components. Examples of such dicarboxylic acid components include dodecanoic acid, eicosanoic acid, dimer acids, and their derivatives.

[0090] The proportion of other dicarboxylic acid components (X3) in the dicarboxylic acid components constituting the copolyester (a1) is, for example, 10 mol% or less, preferably 5 mol% or less, more preferably 3 mol% or less, and most preferably 0 mol%.

[0091] Examples of aliphatic diols (Y) include: ethylene glycol, 1,4-butanediol, 1,4-hexanediol, 1,6-hexanediol, diethylene glycol, trimethylenediol, pentamethylenediol, octamethylenediol, decamethylenediol, neopentyl glycol, 2-ethyl-2-butyl-1,3-propanediol, and other chain-like aliphatic diols; 1,2-cyclohexanediol, 1,1-cyclohexanediethanol, 1,4-cyclohexanediethanol, 2,5-norbornanediethanol, and other alicyclic diols; and aliphatic dimerized diols. They may contain one or more of these diols, or a mixture of two or more.

[0092] From the viewpoint of flexibility, the aliphatic diol is preferably an aliphatic diol with 2 to 8 carbon atoms, more preferably an aliphatic diol with 4 to 8 carbon atoms, and even more preferably an aliphatic diol with 4 to 6 carbon atoms. Furthermore, the aliphatic diol is preferably a chain-like aliphatic diol.

[0093] As an aliphatic diol, more specifically, it is preferably at least one selected from ethylene glycol, diethylene glycol, 1,4-butanediol, 1,4-hexanediol, and 1,6-hexanediol.

[0094] Copolyester (a1) may contain diols other than aliphatic diols (Y) as diol components. Examples of diol components other than aliphatic diols (Y) include: benzenediethanol, 4,4'-dihydroxybiphenyl, 2,2-bis(4'-hydroxyphenyl)propane, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, bis(4-β-hydroxyethoxyphenyl)sulfonic acid, etc.; aromatic diols such as ethylene oxide adducts or propylene oxide adducts of 2,2-bis(4'-hydroxyphenyl)propane, and aromatic dimer glycols.

[0095] The proportion of aliphatic diol (Y) in the diol component constituting the copolyester (a1) is, for example, 50 mol% or more and 100 mol% or less, preferably 70 mol% or more and 100 mol% or less, and more preferably 90 mol% or more and 100 mol% or less. The copolyester (a1) preferably has thermoplastic properties.

[0096] (Copolyester (a1-1))

[0097] As an option, the copolyester (a1) is preferably a copolyester containing an aliphatic diol other than ethylene glycol (Y1) as an aliphatic diol component (Y) (hereinafter also referred to as copolyester (a1-1)), wherein, more preferably, it is a copolyester (a1-1) containing an aliphatic diol (Y2) with 4 to 8 carbon atoms as an aliphatic diol component (Y).

[0098] The copolyester (a1-1) further preferably contains at least 1,4-butanediol as an aliphatic diol component (Y). Furthermore, in the copolyester (a1-1), two or more aliphatic diols (Y) are preferably used. When using two or more, the aliphatic diol (Y) preferably contains two or more aliphatic diols with 4 to 8 carbon atoms, and more preferably contains 1,4-butanediol and 1,6-hexanediol. Using two or more aliphatic diols (Y) further facilitates the reduction of hardness. When 1,4-butanediol and 1,6-hexanediol are included as aliphatic diols (Y), their mass ratio (1,4-butanediol / 1,6-hexanediol) is preferably 10 / 90 to 70 / 30, more preferably 20 / 80 to 60 / 40, and even more preferably 30 / 70 to 50 / 50.

[0099] The proportion of aliphatic diols with 4 to 8 carbon atoms in the diol component constituting the copolyester (a1-1) is, for example, 50 mol% or more and 100 mol% or less, preferably 70 mol% or more and 100 mol% or less, and more preferably 90 mol% or more and 100 mol% or less.

[0100] Furthermore, the copolyester (a1-1) preferably uses an aliphatic dicarboxylic acid with 4 to 10 carbon atoms as the dicarboxylic acid component (X2), with adipic acid being the most preferred. The copolyester (a1-1) preferably has thermoplasticity.

[0101] (Copolyester (a1-2))

[0102] As another option, the copolyester (a1) is preferably a copolyester containing ethylene glycol as an aliphatic diol component (Y) (hereinafter also referred to as copolyester (a1-2)).

[0103] The diol component in the copolyester (a1-2) can be an ethylene glycol monomer, or it can contain diol components other than ethylene glycol. Specific examples of diol components other than ethylene glycol are, as described in copolyester (a1), preferably aliphatic diols (Y2) having 4 to 8 carbon atoms.

[0104] The proportion of ethylene glycol in the diol component constituting the copolyester (a1-2) is, for example, 50 mol% or more and 100 mol% or less, preferably 70 mol% or more and 100 mol% or less, and more preferably 90 mol% or more and 100 mol% or less.

[0105] In addition, the copolyester (a1-2) preferably uses an aromatic dicarboxylic acid as the dicarboxylic acid component (X2) with 4 to 10 carbon atoms, among which isophthalic acid is preferred.

[0106] The copolyester (a1-2) is preferably thermoplastic.

[0107] (Copolyester (a2))

[0108] Furthermore, another example of copolyester (a) is copolyester (a2), which is a copolymer of terephthalic acid (X1) and a diol component containing two or more aliphatic diols (Y). As a specific example of the aliphatic diol (Y), as described above, an aliphatic diol with 4 to 8 carbon atoms is preferred. It is also preferable to use an aliphatic diol with 4 to 8 carbon atoms and ethylene glycol together. On the other hand, the dicarboxylic acid component is preferably formed from the terephthalic acid (X1) monomer, but may also contain other dicarboxylic acids. Copolyester (a2) preferably has thermoplastic properties.

[0109] [Homogeneous polyester (b)]

[0110] This film may contain homopolymer (b). By containing homopolymer (b), the mechanical strength (Young's modulus, etc.) and heat resistance of this film are easily improved. Examples of homopolymer (b) include polymers of terephthalic acid (X1) and any one of the diol components of an aliphatic diol (Y).

[0111] Specific examples of aliphatic diols (Y) are as described above, wherein the aliphatic diol (Y) is preferably any one of aliphatic diols having 2 to 8 carbon atoms. More specifically, the aliphatic diol is preferably any one of ethylene glycol, diethylene glycol, 1,4-butanediol, 1,4-hexanediol, 1,6-hexanediol, or 1,4-cyclohexanediethanol, more preferably ethylene glycol or 1,4-cyclohexanediethanol.

[0112] As a homopolymer polyester, polyethylene terephthalate (PET) with terephthalic acid (X1) as the dicarboxylic acid component and ethylene glycol (Y1) as the glycol component is preferred. However, in PET described as a homopolymer polyester, the glycol component may inevitably contain diethylene glycol. Specifically, in PET (homogeneous polyester), the proportion of diethylene glycol in the glycol component may be, for example, 5 mol% or less, or 3 mol% or less.

[0113] It should be noted that, regarding diethylene glycol, when ethylene glycol is used as one of the raw materials to manufacture (condensation) polyester, a portion of the ethylene glycol will be modified to form diethylene glycol which is then introduced into the polyester backbone.

[0114] Additionally, as a polyester (b), a polymer of terephthalic acid (X1) and 1,4-cyclohexanediethanol, namely polycyclohexanediethanol terephthalate, can also be listed.

[0115] The homopolymer (b) preferably has thermoplasticity.

[0116] [Polyaryl ester (c)]

[0117] This film, based on the aforementioned copolyester (a) or copolyester (a) and homopolymer (b), may also contain polyarylate (c). By using the aforementioned copolyester (a), the glass transition temperature (Tg) of this film becomes easier to lower, while by mixing in polyarylate (c), a film with a high glass transition temperature can be obtained. Therefore, it is possible to suppress breakage during stretching and improve processability. Furthermore, films with excellent heat resistance are readily obtained.

[0118] Polyaryl ester (c) is a condensation polymer of a dicarboxylic acid component (c-1) and a diphenol component (c-2). The glass transition temperature of polyaryl ester (c) can be adjusted by appropriately selecting the dicarboxylic acid component (c-1) and the diphenol component (c-2), especially by appropriately selecting the diphenol component.

[0119] As the dicarboxylic acid component (c-1) constituting the polyarylate (c), there are no particular restrictions as long as it is a diaromatic carboxylic acid, among which a mixture of terephthalic acid and isophthalic acid is preferred.

[0120] The mixing ratio (molar percentage) of terephthalic acid to isophthalic acid is preferably 99 / 1 to 1 / 99, more preferably 90 / 10 to 10 / 90, further preferably 80 / 20 to 20 / 80, particularly preferably 70 / 30 to 30 / 70, and especially preferably 60 / 40 to 40 / 60.

[0121] By adjusting the mixing ratio of terephthalic acid and isophthalic acid, which are dicarboxylic acid components (c-1), to the range described above, polyarylate (c) exhibits excellent heat resistance and melt molding properties.

[0122] In the polyarylate (c), as a dicarboxylic acid component, acid components other than terephthalic acid and isophthalic acid can also be copolymerized.

[0123] Specifically, examples include: aromatic dicarboxylic acids such as phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, benzophenone dicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 3,3'-diphenyldicarboxylic acid, and 4,4'-diphenyl ether dicarboxylic acid; and aliphatic dicarboxylic acids such as cyclohexanedicarboxylic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, and sebacic acid. To avoid impairing the heat resistance of the polyarylate resin (B), the copolymerization ratio of acid components other than the diaromatic carboxylic acids is preferably less than 10 mol%.

[0124] As the diphenol component (c-2) constituting the polyarylate (c), there are no particular limitations as long as it is a diphenol, but it is preferred to include either bisphenol A, bisphenol TMC (1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane), or both bisphenol A and bisphenol TMC.

[0125] Typically, by including bisphenol A, polyarylates exhibit excellent melt moldability (flowability). On the other hand, by containing bisphenol TMC, polyarylates exhibit increased glass transition temperature and excellent heat resistance (c).

[0126] Both bisphenol A and bisphenol TMC components are used to achieve a balance between melt formability and heat resistance.

[0127] In this case, the ratio (molar percentage) of bisphenol A to bisphenol TMC is preferably bisphenol A / bisphenol TMC = 99 / 1 to 1 / 99, more preferably 90 / 10 to 10 / 90, further preferably 80 / 20 to 20 / 80, particularly preferably 70 / 30 to 30 / 70, and especially preferably 60 / 40 to 40 / 60.

[0128] By keeping the ratio of bisphenol A to bisphenol TMC within the above range, a polyarylate (c) with excellent balance between heat resistance and melt moldability is obtained.

[0129] In the polyarylate (c), as the diphenol component (c-2), other bisphenol components besides bisphenol A (2,2-bis(4-hydroxyphenyl)propane) and bisphenol TMC (1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane) can also be copolymerized. Specifically, examples include: bisphenol AP (1,1-bis(4-hydroxyphenyl)-1-phenylethane), bisphenol AF (2,2-bis(4-hydroxyphenyl)hexafluoropropane), bisphenol B (2,2-bis(4-hydroxyphenyl)butane), bisphenol BP (bis(4-hydroxyphenyl)diphenylmethane), bisphenol C (2,2-bis(3-methyl-4-hydroxyphenyl)propane), bisphenol E (1,1-bis(4-hydroxyphenyl)ethane), and bisphenol F (bis(4-hydroxyphenyl)methane). Bisphenol G (2,2-bis(4-hydroxy-3-isopropylphenyl)propane), bisphenol M (1,3-bis(2-(4-hydroxyphenyl)-2-propyl)benzene), bisphenol S (bis(4-hydroxyphenyl)sulfone), bisphenol P (1,4-bis(2-(4-hydroxyphenyl)-2-propyl)benzene), bisphenol PH (5,5'-(1-methylethoxy)-bis[1,1'-(bisphenyl)-2-ol]propane), bisphenol Z (1,1-bis(4-hydroxyphenyl)cyclohexane), etc. To avoid impairing the heat resistance of the polyarylate (c), the copolymerization ratio of the above compounds is preferably less than 10 mol%.

[0130] In the polyarylate (c), the preferred dicarboxylic acid component (c-1) is a mixture of terephthalic acid and isophthalic acid, and the preferred diphenol component (c-2) is either bisphenol A, bisphenol TMC, or a mixture of bisphenol A and bisphenol TMC.

[0131] As for polyarylate (c), it can also be used in combination with polycarbonate to improve melt moldability. Since polyarylate (c) is miscible with polycarbonate, by mixing polycarbonate into polyarylate (c), the glass transition temperature of polyarylate (c) can be lowered while maintaining transparency and mechanical properties, and ultimately the melt moldability can be improved.

[0132] When polyarylene (c) is mixed with polycarbonate, the mixing ratio (mass%) is preferably polyarylene (c) / polycarbonate = 99 / 1 to 50 / 50, more preferably 98 / 2 to 60 / 40, further preferably 97 / 3 to 70 / 30, and particularly preferably 96 / 5 to 80 / 20.

[0133] If the mixing ratio of polyarylate (c) to polycarbonate is within the above range, the melt moldability can be improved while maintaining the heat resistance of polyarylate (c).

[0134] It should be noted that, regarding the mixing of polyarylate (c) and polycarbonate, it is preferable to use a substance obtained by pre-mixing the two components as a raw material, but it is not limited to this method. Polycarbonate can also be selected as another resin and used as a separate raw material to form the above-mentioned composition.

[0135] Additionally, the polycarbonate mixed in polyarylate (c) is not included in the content of polyarylate (c).

[0136] (Thickness of the film)

[0137] The thickness of this thin film is not particularly limited, but is, for example, 20 μm or more and 250 μm or less, preferably 30 μm or more and 220 μm or less, more preferably 35 μm or more and 200 μm or less, even more preferably 40 μm or more and 180 μm or less, and even more preferably 45 μm or more and 120 μm or less. By keeping the thickness of the thin film within the above-mentioned range, the chip and wafer can be properly protected during the semiconductor manufacturing process without exceeding the required thickness.

[0138] This film can be a stretched film or a non-stretched film, but a stretched film is preferred. The stretched film can also be a uniaxial stretched film, but a biaxial stretched film is preferred. By using a stretched film, it is easy to improve mechanical strengths such as Young's modulus. The stretched film is preferably a co-extruded stretched film formed by co-extrusion.

[0139] [Layered structure]

[0140] This film can be a single-layer film with a single-layer structure or a multi-layer film with a multi-layer structure, but is preferably a multi-layer film. In the case of a multi-layer film, it is preferable to have an intermediate layer (B) and a surface layer (A) disposed on at least one side of the intermediate layer (B), and it is even more preferable to have the surface layer (A) disposed on both sides of the intermediate layer (B). Therefore, this film can also be a 2-layer structure of intermediate layer (B) / surface layer (A), but is preferably a 3-layer structure of surface layer (A) / intermediate layer (B) / surface layer (A). In addition, as long as the surface layer is located on the surface of the film, it is not limited to a 2-layer or 3-layer structure, and can also have a 4-layer or more layer structure with two or more intermediate layers (B).

[0141] This thin film, by having a surface layer (A), can reduce surface hardness using the surface layer (A) while imparting high mechanical strength such as Young's modulus using the intermediate layer (B). Furthermore, by having surface layers (A) on both sides, this thin film can contain layers with low hardness on both sides. Therefore, as described above, this thin film can also relax stress on one side while filling in unevenness caused by foreign matter on the other side, thereby further preventing cracks in wafers and chips.

[0142] In the multilayer film, at least one surface layer (A), preferably two surface layers (A), contains thermoplastic polyester. Additionally, the intermediate layer (B) in the multilayer film also preferably contains thermoplastic polyester. By containing thermoplastic polyester in the intermediate layer (B), the recyclability of the film can be improved while simultaneously increasing mechanical strengths such as Young's modulus.

[0143] The thickness of each surface layer (A) in the multilayer film is preferably 1% or more and 25% or less of the overall thickness of the film, more preferably 3% or more and 20% or less, and even more preferably 5% or more and 15% or less. If the thickness of the surface layer (A) is within this range, stress relaxation can be appropriately achieved through the surface layer (A) with low surface hardness without compromising the overall mechanical strength of the film.

[0144] Furthermore, from the same point of view, the thickness of each surface layer (A) in the multilayer film is, for example, 2 μm or more and 40 μm or less, preferably 3 μm or more and 30 μm or less, more preferably 3.5 μm or more and 20 μm or less, and even more preferably 4 μm or more and 15 μm or less.

[0145] The thickness of the intermediate layer (B) in the multilayer film is preferably 60% or more and 98% or less of the overall thickness of the film, more preferably 70% or more and 96% or less, and even more preferably 75% or more and 92% or less. If the thickness of the intermediate layer (B) is within this range, it is possible to impart appropriate mechanical strength to the film as a whole through the intermediate layer (B) while properly relaxing stress through the surface layer (A).

[0146] From the same point of view, the thickness of the intermediate layer (B) in the multilayer film is, for example, 10 μm or more and 200 μm or less, preferably 20 μm or more and 150 μm or less, more preferably 25 μm or more and 125 μm or less, even more preferably 30 μm or more and 100 μm or less, and even more preferably 40 μm or more and 80 μm or less.

[0147] In the case of a single-layer film, the single-layer film itself constitutes the surface layer (A). That is, in the case of a single-layer film, this film can be said to be a film formed by the surface layer (A) constituting the two surfaces of this film.

[0148] In this invention, the film may contain a copolyester on one surface, preferably on both surfaces. Therefore, in a multilayer film, the surface layer (A) may contain a copolyester, and when the surface layer (A) is disposed on both sides of the film, both surface layers (A) preferably contain a copolyester. By containing a copolyester on the surface of the film, i.e., the surface layer (A), as described above, the hardness of one or both surfaces of the film is easily reduced. Here, the copolyester contained on the surface is preferably the aforementioned copolyester (a).

[0149] Similarly, in a single-layer film, the film (i.e., the surface layer (A)) preferably contains a copolyester, and more preferably contains the aforementioned copolyester (a).

[0150] The content of copolyester (a) on each surface of the film can be adjusted to reach the specified range of the proportions of the components (A1), (A4), etc., as described later, without any particular limitation. For example, it can be 10% by mass or more and 97% by mass or less, preferably 10% by mass or more and 90% by mass or less, more preferably 15% by mass or more and 85% by mass or less, even more preferably 20% by mass or more and 70% by mass or less, and even more preferably 25% by mass or more and 60% by mass or less.

[0151] It should be noted that the content of copolyester (a) in each surface refers to the content of copolyester (a) in the surface layer (A) of a multilayer film, and to the content of copolyester (a) in the entire film (i.e., the surface layer (A)) when there is no gradient in the blending. Furthermore, even though this film is a single-layer film, as will be described later, the blending may sometimes gradually change along the thickness direction, and thus the content of (a) may sometimes change along the thickness direction. In this case, the content of (a) in the surface can be determined by sampling, for example, from the area from the film surface to 10% of the overall thickness, using a known measurement method. The same applies to the contents of components (b), (c), etc.

[0152] This film preferably contains both copolyester (a) and homopolymer (b) on one surface, and more preferably, both surfaces contain both copolyester (a) and homopolymer (b). Therefore, in a multilayer film, it is preferable that the surface layer (A) contains both copolyester (a) and homopolymer (b), and when the surface layer (A) is provided on both sides of the film, it is preferable that both surface layers (A) contain both copolyester (a) and homopolymer (b). By containing both copolyester (a) and homopolymer (b) on the surface of the film, i.e., the surface layer (A), this film can easily improve mechanical strengths such as Young's modulus while reducing the hardness of one or two surfaces of the film.

[0153] Similarly, in a single-layer film, the film (i.e., the surface layer (A) constituting the single-layer film) preferably contains homopolymer polyester (b) in addition to copolyester (a).

[0154] In each surface of this film, the content of homopolymer polyester (b) is not particularly limited as long as the proportions of the components described later (A1), (A4), etc., are adjusted to reach the specified range. For example, it can be 0% by mass or more and 90% by mass or less, preferably 5% by mass or more and 85% by mass or less, more preferably 8% by mass or more and 70% by mass or less, and even more preferably 10% by mass or more and 65% by mass or less. It should be noted that 0% by mass means that homopolymer polyester (b) is not present. The same applies below.

[0155] This film may contain polyarylate (c) in addition to copolyester (a), or copolyester (a) and homopolymer (b) on one surface, or polyarylate (c) in addition to copolyester (a), or copolyester (a) and homopolymer (b) on both surfaces. Therefore, in a multilayer film, the surface layer (A) may contain copolyester (a) and polyarylate (c), or copolyester (a), homopolymer (b) and polyarylate (c). When the surface layer (A) is provided on both sides of the film, both surface layers (A) may contain copolyester (a) and polyarylate (c), or copolyester (a), homopolymer (b) and polyarylate (c).

[0156] This film, by containing polyarylate (c) on its surface, can increase the glass transition temperature of the film surface even when containing copolyester (a). Therefore, the difference in glass transition temperature between the film and the intermediate layer (B) can be reduced, making it less prone to process defects. Furthermore, the overall glass transition temperature of the film can be increased, thus improving its heat resistance.

[0157] In addition, in the monolayer film, the film (i.e., the surface layer (A) constituting the monolayer film) may also contain polyarylate (c) in addition to copolyester (a) and homopolymer (b).

[0158] The content of polyarylate (c) is not particularly limited as long as the proportions of the components described later (A1), (A4), etc., are adjusted to reach the specified range. Preferably, it is 55% by mass or less, more preferably 50% by mass or less, and even more preferably 45% by mass or less. In addition, the content of polyarylate (c) on each surface of the film is 0% by mass or more. When polyarylate (c) is present on each surface of the film, in order to properly exert the synergistic effect, it is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more.

[0159] In this invention, the film may contain at least one of copolyester (a) and homopolymer (b) in the central portion of the film thickness direction, but it is preferred to contain both. Alternatively, the central portion of the film thickness direction may also contain polyarylate (c) in addition to at least one of copolyester (a) and homopolymer (b).

[0160] Therefore, in the multilayer film, the intermediate layer (B) may contain at least one of copolyester (a) and homopolymer (b), but preferably at least copolyester (a), more preferably both. In addition, the intermediate layer (B) may also contain polyarylate (c).

[0161] By including homopolymer (b) in the intermediate layer (B), the film's mechanical strength, such as Young's modulus, is easily improved. Furthermore, by including copolyester (a) and polyarylate (c), the composition of the central portion of the film in the thickness direction (i.e., the intermediate layer (B)) is easily made similar to the composition of the film surface (i.e., the surface layer (A)). Therefore, stretching and other processes are easier to perform in the manufacturing process, increasing productivity. Additionally, the interlayer adhesion strength between the intermediate layer (B) and the surface layer (A) is also easily improved.

[0162] The content of copolyester (a) in the central part of the film thickness direction is preferably less than the content of copolyester (a) in the surface. Furthermore, this can be achieved by adjusting the proportions of the components described later (B1), (B4), etc., to within the specified range.

[0163] The content of copolyester (a) in the central portion of the film in the thickness direction is not particularly limited, but is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 30% by mass or less, and even more preferably 20% by mass or less. Furthermore, the content of copolyester (a) in the central portion of the film in the thickness direction can be 0% by mass or more, preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more.

[0164] It should be noted that the content of copolyester (a) in the central part of the thickness direction mentioned above refers to the content of copolyester (a) in the intermediate layer (A) of multilayer films. Furthermore, even in single-layer films, as described later, the composition sometimes gradually changes along the thickness direction, and the content of (a) also varies along the thickness direction. In this case, it is sufficient for the content of copolyester (a) in the central part of the thickness direction to reach the range mentioned above.

[0165] It should be noted that, in the case of non-multilayer thin films, the content of component (a) in the central part can be determined by sampling from a region equivalent to 10% of the overall thickness, centered on the center of the film thickness, and using a known measurement method. The same applies to the contents of components (b), (c), etc.

[0166] The content of homopolymer (b) in the central part of the film in the thickness direction is preferably greater than the content of homopolymer (b) in the surface. In addition, it is acceptable as long as the proportions of the components (B1), (B4), etc., described later are adjusted to reach the specified range.

[0167] The content of homopolymer (b) in the central portion of the film in the thickness direction is not particularly limited, but is preferably 40% by mass or more, more preferably 50% by mass or more, further preferably 70% by mass or more, and even more preferably 80% by mass or more. Furthermore, the content of homopolymer (b) in the central portion of the film in the thickness direction can be 100% by mass or less, preferably 99% by mass or less, more preferably 97% by mass or less, and even more preferably 95% by mass or less.

[0168] The content of polyarylate (c) in the central part of the film in the thickness direction is preferably less than the content of polyarylate (c) in the surface. In addition, it is acceptable as long as the proportions of the components (B1), (B4), etc., described later are adjusted to reach the specified range.

[0169] The content of polyarylate (c) in the central part of the film thickness direction is not particularly limited, but is preferably 40% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less, and even more preferably 10% by mass or less.

[0170] The content of polyarylate (c) in the central part of the thickness direction can be 0% by mass or more. When the central part of the film contains polyarylate (c), its content should preferably be a certain value or more, preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more.

[0171] [The proportions of each component in the surface (surface layer (A))]

[0172] In this film, when the proportion (molar percentage) of dicarboxylic acid components (excluding terephthalic acid) with 4 to 10 carbon atoms in the total polyester content of a surface is defined as (A1), and the proportion (molar percentage) of diol components (excluding ethylene glycol) in the total polyester content of a surface is defined as (A4), (A1) + (A4) is preferably 5 mol% or more, more preferably 8 mol% or more, further preferably 15 mol% or more, and even more preferably 25 mol% or more. By making (A1) + (A4) a certain value or more as described above, it is easy to reduce the hardness of a surface and to improve stress relaxation characteristics.

[0173] The upper limit of (A1) + (A4) is not particularly limited, but from the viewpoint of easily improving the mechanical strength, heat resistance and other properties of the film, it is preferably 150 mol% or less, more preferably 130 mol% or less, even more preferably 120 mol% or less, and even more preferably 110 mol% or less.

[0174] Regarding the proportions (A1), (A4) in one surface and the proportions (A2), (A3), (A5) to (A7) described later, in a multilayer structure, these refer to the proportions in the surface layer (A). Therefore, in the case of a multilayer structure, it is preferable that one surface layer (A) satisfies the requirements for each proportion (A1) to (A7) as described above or later, and it is more preferable that two surface layers (A) satisfy the requirements for each proportion (A1) to (A7) as described above or later.

[0175] Furthermore, if the film is a single-layer structure and the fit does not gradually change as described later, the above or later specifications for the proportions (A1) to (A7) in a single surface should be used as specifications for the proportions (A1) to (A7) in the entire film (i.e., the surface layer (A) in the single-layer film).

[0176] Furthermore, as will be described later, the composition of this film varies gradually, and therefore the values ​​of the proportions (A1) to (A7) described above or later may vary along the thickness direction. Regarding the proportions of each component on the surface in this case, for example, samples can be taken from a region extending from the film surface to 10% of the overall thickness, and each proportion can be determined using known measurement methods.

[0177] In this film, when the proportion (molar percentage) of polyarylate (c) and dicarboxylic acid components with 4 to 10 carbon atoms (excluding terephthalic acid) in the total polyester contained in a surface (i.e., surface layer (A)) is set as (A2); and when the proportion (molar percentage) of polyarylate (c) and diol components (excluding ethylene glycol) in the total polyester contained in a surface (i.e., surface layer (A)) is set as (A5), (A2) + (A5) is preferably 5 mol% or more, more preferably 8 mol% or more, further preferably 15 mol% or more, and even more preferably 25 mol% or more. By making (A1) + (A4) a certain value or more as described above, it is easy to reduce the hardness of a surface and easy to improve stress relaxation characteristics.

[0178] (A2) + (A5) is not particularly limited, but from the viewpoint of easily improving the mechanical strength and heat resistance of the film, it is preferably 100 mol% or less, more preferably 90 mol% or less, further preferably 80 mol% or less, and even more preferably 70 mol% or less.

[0179] From the viewpoint of easily reducing the hardness of a surface, the aforementioned proportion (A1) is preferably 3 mol% or more, more preferably 5 mol% or more, further preferably 10 mol% or more, and even more preferably 15 mol% or more. Furthermore, from the viewpoint of easily containing a certain amount or more of terephthalic acid (X1) in a surface, the proportion (A1) is preferably 50 mol% or less, more preferably 40 mol% or less, further preferably 35 mol% or less, and even more preferably 32 mol% or less.

[0180] The aforementioned proportion (A2) is preferably 2 mol% or more. By making the proportion (A2) 2 mol% or more, it is easier to reduce the hardness of a surface and to improve stress relaxation characteristics. The proportion (A2) is more preferably 3 mol% or more, further preferably 4 mol% or more, and even more preferably 5 mol% or more.

[0181] Furthermore, from the viewpoint that a certain amount or more of terephthalic acid (X1) is easily contained in a single surface, the proportion (A2) is preferably 50 mol% or less, more preferably 40 mol% or less, even more preferably 30 mol% or less, and even more preferably 20 mol% or less.

[0182] In this film, the proportion (A3) of aliphatic dicarboxylic acid components with 4 to 10 carbon atoms in the total polyester content of one surface (i.e., surface layer (A)) is preferably 2 mol% or more. By making the proportion (A3) 2 mol% or more, it is easy to reduce the hardness of one surface and easy to improve stress relaxation characteristics. The proportion (A3) is more preferably 3 mol% or more, further preferably 4 mol% or more, and even more preferably 5 mol% or more.

[0183] Furthermore, from the viewpoint that a certain amount or more of terephthalic acid (X1) is easily contained in a single surface, the proportion (A3) is preferably 30 mol% or less, more preferably 20 mol% or less, even more preferably 15 mol% or less, and even more preferably 10 mol% or less.

[0184] In this thin film, the above-mentioned proportion (A4) is 0 mol% or more, preferably 5 mol% or more, more preferably 10 mol% or more, and even more preferably 20 mol% or more. In addition, the proportion (A4) is preferably 95 mol% or less, more preferably 90 mol% or less, even more preferably 85 mol% or less, and even more preferably 80 mol% or less.

[0185] In addition, the above-mentioned proportion (A5) can be 0 mol% or more, preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 20 mol% or more, and preferably 70 mol% or less, more preferably 65 mol% or less, even more preferably 60 mol% or less, and even more preferably 55 mol% or less.

[0186] In this film, the proportion (A6) of terephthalic acid in the total polyester contained in one surface (i.e., surface layer (A)) is preferably 50 mol% or more, more preferably 60 mol% or less, even more preferably 65 mol% or more, and even more preferably 68 mol% or more. Furthermore, the proportion (A6) is preferably 97 mol% or less, more preferably 95 mol% or more, even more preferably 90 mol% or more, and even more preferably 85 mol% or more.

[0187] In this film, the proportion (A7) of ethylene glycol in the total polyester content of one surface (i.e., surface layer (A)) is preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 15 mol% or more, and even more preferably 20 mol% or more. The proportion (A7) can be 100 mol% or less, more preferably 95 mol% or less, even more preferably 90 mol% or less, and even more preferably 80 mol% or less.

[0188] [The proportions of each component in the center (intermediate layer (B)) in the thickness direction]

[0189] In this film, when the proportion (molar percentage) of dicarboxylic acid components (excluding terephthalic acid) with 4 to 10 carbon atoms in the total polyester contained in the thickness direction at the center is set as (B1), and the proportion (molar percentage) of diol components (excluding ethylene glycol) in the total polyester contained in the thickness direction at the center is set as (B4), in one embodiment, it is preferable that (A1) + (A4) is higher than (B1) + (B4). By making (A1) + (A4) higher than (B1) + (B4), it is easy to reduce the surface hardness of the film while maintaining a certain level of mechanical strength, thereby imparting stiffness and other properties to the film. The difference between [(A1) + (A4)] and [(B1) + (B4)] is preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 15 mol%, and even more preferably 30 mol% or more. In addition, it is preferably 140 mol% or less, more preferably 120 mol% or less, even more preferably 110 mol% or less, and even more preferably 100 mol% or less.

[0190] It should be noted that, in one embodiment of the present invention, when (A1) + (A4) is higher than (B1) + (B4), the hardness of one surface of the film should preferably be below 450 MPa. However, in the present invention, the hardness may not necessarily be below 450 MPa.

[0191] Furthermore, from the viewpoint of improving the mechanical strength and heat resistance of the film, the concentration of (B1) + (B4) should preferably be below a certain value, preferably below 30 mol%, more preferably below 20 mol%, further preferably below 15 mol%, and even more preferably below 10 mol%. While (B1) + (B4) can be 0 mol% or more, from the viewpoint of closely approximating the composition of the surface layer (A) and facilitating stretching, it should preferably be above a certain value, preferably above 2 mol%, more preferably above 4 mol%, and even more preferably above 6 mol%.

[0192] Regarding the proportions (B1), (B4) of the center portion in the thickness direction and the proportions (B2), (B3), (B5) to (B7) described later, in a multilayer structure, these refer to the proportions in the intermediate layer (B). Therefore, in the case of a multilayer structure, it is preferable that the intermediate layer (B) meets the requirements for each proportion (B1) to (B7) as described above or later.

[0193] Furthermore, even if this film is a single-layer film, as described later, the composition may sometimes change, and thus the values ​​of the proportions (B1) to (B7) mentioned above or later may sometimes vary along the thickness direction. Regarding the proportions of each component in the central part in this case, for example, a sample of 10% of the overall thickness can be taken with the central part in the thickness direction as the center, and the content of each component can be determined by a known measurement method.

[0194] In this film, when the proportion (molar percentage) of polyarylate (c) and dicarboxylic acid components with 4 to 10 carbon atoms (excluding terephthalic acid) in the total polyester contained in the central portion (i.e., the intermediate layer (B)) in the thickness direction is set as (B2); and when the proportion (molar percentage) of polyarylate (c) and diol components (excluding ethylene glycol) in the total polyester contained in the central portion (i.e., the intermediate layer (B)) in the thickness direction is set as (B5), it is preferable that (A2) + (A5) is higher than (B2) + (B5). By making (A2) + (A5) higher than (B2) + (B5), it is easy to reduce the surface hardness of the film while maintaining a certain level of mechanical strength, thereby imparting stiffness and other properties to the film. The difference between [(B2) + (B5)] and [(A2) + (A5)] is preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 15 mol% or more, and preferably 90 mol% or less, more preferably 80 mol% or less, and even more preferably 60 mol% or less.

[0195] Furthermore, from the viewpoint of ensuring the mechanical strength of the film is at a certain level and imparting stiffness to the film, the concentration of (B2) + (B5) should preferably be at a certain level or lower, preferably 30 mol% or lower, more preferably 20 mol% or lower, even more preferably 15 mol% or lower, and even more preferably 10 mol% or lower. While (B2) + (B5) can be at least 0 mol%, from the viewpoint of closely approximating the composition of the surface layer (A) and facilitating stretching, it should preferably be at a certain value or higher, preferably 2 mol% or higher, more preferably 4 mol% or higher, and even more preferably 6 mol% or higher.

[0196] In this film, the proportion (B3) of aliphatic dicarboxylic acid components with 4 to 10 carbon atoms in all polyester components contained in the thickness direction (i.e., the intermediate layer (B)) is preferably lower than the proportion (A3) mentioned above. By making (B3) lower than (A3), it is easier to improve the mechanical strength, heat resistance, etc. of the film while reducing the surface hardness of the film. The proportion (B3) is more preferably 1 to 25 mol% lower than (A3), more preferably 2 to 15 mol% lower, and even more preferably 3 to 10 mol% lower.

[0197] The specific value of the proportion (B3) is not particularly limited, and it can be 0 mol% or more. However, from the viewpoint of being close to the composition of the surface layer (A) and facilitating stretching, it is preferable to be a certain value or more, such as 0.5 mol% or more, or 1 mol% or more. In addition, the proportion (B3) can be, for example, 8 mol% or less, preferably 4 mol% or less, and more preferably 3 mol% or less.

[0198] In this thin film, the proportions (B4) and (B5) are not particularly limited and can be 0 mol% or more. However, from the viewpoint of approximating the composition of the surface layer (A), they can be 2 mol% or more or 4 mol% or more. In addition, from the viewpoint of improving the mechanical strength and heat resistance of the thin film, the proportion (B4) is preferably 20 mol% or less, more preferably 15 mol% or less, and even more preferably 10 mol% or less.

[0199] In this film, from the viewpoint of improving mechanical strength and heat resistance, the proportion (B6) of terephthalic acid in the total polyester contained in the center portion (i.e., the intermediate layer (B)) in the thickness direction is preferably 70 mol% or more, more preferably 80 mol% or less, further preferably 90 mol% or more, and even more preferably 95 mol% or more. Additionally, the proportion (A6) can be 100 mol% or less, and can be 99.5 mol% or less, or 99 mol% or less.

[0200] In this film, the proportion (B7) of ethylene glycol in the total polyester contained in the center portion (i.e., the intermediate layer (B)) in the thickness direction is preferably 55 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and even more preferably 90 mol% or more. In addition, the proportion (B7) can be 100 mol% or less, more preferably 99 mol% or less, and even more preferably 96 mol% or less.

[0201] The film is preferably made of polyester as the main component, and the content of polyester relative to the total film is, for example, 65% by mass or more, preferably 70% by mass or more, and more preferably 80% by mass or more.

[0202] In addition, the polyester content in the surface (i.e., the surface layer (A)) is, for example, 65% by mass or more, preferably 70% by mass or more, more preferably 80% by mass or more, and preferably 100% by mass or less. However, from the viewpoint of containing other components such as impact resistance modifiers, it is preferably 99.9% by mass or less, more preferably 99% by mass or less, and even more preferably 98% by mass or less.

[0203] On the other hand, the polyester content in the center part in the thickness direction (i.e., the intermediate layer (B)) can be, for example, 70% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and can be 100% by mass or less, but from the viewpoint of containing other components, it can also be less than 100% by mass.

[0204] [Impact resistance modifier]

[0205] This film may also contain an impact-resistant modifier. Preferably, the impact-resistant modifier is contained on one surface (i.e., a surface layer (A)). By containing an impact-resistant modifier on the surface of the film (surface layer (A)), the surface hardness is easily reduced, and stress relaxation characteristics are improved.

[0206] In addition, this film preferably contains an impact resistance modifier on both surfaces (i.e., two surface layers (A)). By containing an impact resistance modifier on both surfaces, the stress relaxation characteristics on one surface are improved, while the other surface is made easier to adhere to the adsorption stage, thereby making it easier to further reduce cracks in wafers and chips.

[0207] In addition, even in the case of a single-layer film, the film may contain an impact resistance modifier in the single-layer film (i.e., the surface layer (A)).

[0208] Examples of impact resistance modifiers include soft styrene-based resins and elastomers. The elastomer can also be a core-shell type elastomer. An impact resistance modifier can be used alone or in combination with two or more types. Among the above, core-shell type elastomers are preferred as impact resistance modifiers. Using core-shell type elastomers further improves impact resistance and enhances reliability during long-term use.

[0209] Examples of soft styrene-based resins include block copolymers containing styrene polymer blocks and conjugated diene polymer blocks, and block copolymers containing styrene polymer blocks and acrylonitrile blocks.

[0210] The styrene content in the flexible styrene-based resin is, for example, 5% by mass or more and 80% by mass or less, preferably 10% by mass or more and 50% by mass or less, and more preferably 15% by mass or more and 30% by mass or less. By keeping the styrene content within the above range, the effect of imparting impact resistance is further improved.

[0211] As a conjugated diene polymer block used in soft styrene-based resins, homopolymers of butadiene, isoprene, 1,3-pentadiene, etc., copolymers thereof, or copolymers containing monomers that can copolymerize with conjugated diene monomers within the block can be used.

[0212] Specific examples of flexible styrene-based resins include styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), silicone-acrylic acid composite rubber-acrylonitrile-styrene copolymers (SAS), methyl methacrylate-maleic anhydride-styrene copolymers (SMM), acrylonitrile-styrene copolymers (AS), acrylonitrile-butadiene-styrene copolymers (ABS), acrylonitrile-styrene-acrylic rubber copolymers (ASA), and acrylonitrile-ethylene-propylene rubber-styrene copolymers (AES). Specific products include the "Kraton D" series manufactured by Kraton Polymers, the "AR-100" series manufactured by ARONKASEI, the "DIALAC" series manufactured by UMG ABS, and the "DELPET" series manufactured by Asahi Kasei Chemicals. Furthermore, flexible styrene-based resins, as styrene-based elastomers discussed later, can also include the "DYNARON" series manufactured by JSR, the "Tuftec" series manufactured by Asahi Kasei Chemicals, and the "Hybrar" series manufactured by Kuraray.

[0213] It should be noted that block copolymers include pure blocks, random blocks, and graded blocks, and there is no particular limitation on the copolymerization morphology. Furthermore, the block units can also be multiple overlapping repeating units. Specifically, in the case of styrene-butadiene block copolymers, the block units can be repeated multiple times, as in styrene-butadiene copolymers, styrene-butadiene-styrene block copolymers, and styrene-butadiene-styrene-butadiene block copolymers.

[0214] Alternatively, hydrogenated styrene-butadiene-styrene block copolymers (SEBS) and hydrogenated styrene-isoprene-styrene block copolymers (SEPS) can be used, obtained by hydrogenating part or all of the double bonds in the conjugated diene polymer blocks of SBS and SIS. Specific products include the "Tuftec H" series manufactured by Asahi Kasei Chemicals and the "Kraton G" series manufactured by Kraton Polymers.

[0215] In flexible styrene-based resins, polar functional groups can also be imparted. Specific examples of polar functional groups include anhydride groups, carboxylic acid groups, carboxylic acid ester groups, chlorocarboxylic acid groups, carboxylic acid amide groups, carboxyl salt groups, sulfonic acid groups, sulfonate groups, chlorosulfonic acid groups, sulfonamide groups, sulfonate groups, epoxy groups, amino groups, imide groups, and oxazoline groups. Among these, anhydride groups and epoxy groups are preferred.

[0216] As a soft styrene-based resin endowed with polar functional groups, modified versions of SEBS and SEPS are preferred. Specifically, examples include maleic anhydride-modified SEBS, maleic anhydride-modified SEPS, epoxy-modified SEBS, and epoxy-modified SEPS. Specific products include the "Tuftec M" series manufactured by Asahi Kasei Chemicals, the "DYNARON" series manufactured by JSR Corporation, and the "EPOFRIEND" series manufactured by Daicel Chemical Industries, Ltd.

[0217] In addition, soft styrene-based resins can also be styrene-based elastomers containing elastomer components. Specifically, among the aforementioned substances, block copolymers of styrene with butadiene, isoprene, 1,3-pentadiene, etc., or their modified forms, hydrides, etc., can be listed. More specifically, SBS, SIS, SEBS, SEPS, etc., can be listed.

[0218] The elastomer can be any elastomer other than styrene-based elastomers, including known elastomers such as polyester-based elastomers, polyolefin-based elastomers, diene-based elastomers, acrylic elastomers, polyamide-based elastomers, polyurethane-based elastomers, fluorinated elastomers, and silicone elastomers. The elastomer is typically a thermoplastic elastomer. Polyester-based elastomers or the aforementioned styrene-based elastomers are preferred.

[0219] Polyester-based elastomers are thermoplastic polyesters that exhibit rubber-like properties at room temperature. They are preferably thermoplastic elastomers with polyester block copolymers as the main component, and more preferably block copolymers with high-melting-point, highly crystalline aromatic polyesters as hard segments and amorphous polyesters or amorphous polyethers as soft segments. The soft segment content of the polyester elastomer is at least 20-95 mol% of the total segments, and in the case of a block copolymer of polybutylene terephthalate and polytetramethylene glycol (PTMG-PBT copolymer), it is 50-95 mol%. The soft segment content is preferably 50-90 mol%, and particularly preferably 60-85 mol%. Polyester ether block copolymers, especially PTMG-PBT copolymers, are preferred due to their reduced transmittance.

[0220] A core-shell elastomer consists of an innermost layer (i.e., the core) and one or more outer layers (i.e., the shell) covering it. As a core-shell elastomer, a core-shell graft copolymer obtained by graft copolymerization using a monomer component that can be grafted onto the core as the shell is preferred.

[0221] Core-shell graft copolymers typically use a polymer component, referred to as the rubber component, as the core. In core-shell graft copolymers, it is preferable to graft copolymerize the polymer component constituting the core and the monomer component that can copolymerize with the polymer component, which serves as the shell.

[0222] The manufacturing method for core-shell graft copolymers can be any of the following: bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. The copolymerization can be single-stage or multi-stage grafting. However, commercially available core-shell elastomers can usually be used directly. Examples of commercially available core-shell elastomers are shown below.

[0223] Specific examples of polymer components forming the nucleus include: butadiene-based rubbers such as polybutadiene and styrene-butadiene copolymers; isoprene-based rubbers; acrylic rubbers such as polybutyl acrylate, poly(2-ethylhexyl acrylate), and butyl acrylate / 2-ethylhexyl acrylate copolymers; silicone rubbers such as polysiloxane rubbers; butadiene-acrylic composite rubbers; silicone-acrylic composite rubbers such as IPN (Interpenetrating Polymer Network) type composite rubbers formed from polysiloxane rubbers and polyalkyl acrylate rubbers; ethylene-α-olefin rubbers such as ethylene-propylene copolymers, ethylene-butene copolymers, and ethylene-octene copolymers; ethylene-acrylic rubbers; and fluororubbers. These can be used alone or in combination of two or more. Among these, from the perspective of mechanical properties and surface appearance, at least one selected from butadiene-based rubbers, acrylic rubbers, silicone rubbers, and silicone-acrylic composite rubbers is preferred, and more preferably at least one selected from butadiene-based rubbers and silicone-acrylic composite rubbers.

[0224] Specific examples of monomeric components constituting the shell and capable of graft copolymerization with the polymeric components of the core include: aromatic vinyl compounds; cyanide vinyl compounds; (meth)acrylate compounds, such as (meth)acrylate compounds, (meth)acrylate compounds, glycidyl (meth)acrylate, and other epoxy-containing (meth)acrylate compounds; maleimide compounds such as maleimide, N-methylmaleimide, and N-phenylmaleimide; α,β-unsaturated carboxylic acid compounds such as maleic acid, phthalic acid, and itaconic acid, and their anhydrides (e.g., maleic anhydride). These monomeric components can be used alone or in combination of two or more. Among these, aromatic vinyl compounds, cyanide vinyl compounds, and (meth)acrylate compounds are preferred from the perspective of mechanical properties and surface appearance; more preferably, aromatic vinyl compounds and (meth)acrylate compounds; and especially (meth)acrylate compounds.

[0225] Specific examples of aromatic vinyl compounds include: styrene, α-methylstyrene, 1-vinylnaphthalene, 4-methylstyrene, 4-propylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene or halostyrene, among which styrene or α-methylstyrene is more preferred.

[0226] Specific examples of (meth)acrylate compounds include: methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, etc. Among these, methyl (meth)acrylate and ethyl (meth)acrylate, which are relatively easy to obtain, are preferred, and methyl (meth)acrylate is more preferred. It should be noted that "(meth)acrylate" is a general term for "acrylic acid" and "methacrylic acid".

[0227] As a core-shell type elastomer, a core-shell type graft copolymer formed of a core and a shell is particularly preferred. The core is at least one polymer component selected from butadiene-based rubber, acrylic rubber, silicone rubber, and silicone-acrylic composite rubber. The shell is formed by grafting copolymers of (meth)acrylates and other (meth)acrylate compounds, or aromatic vinyl compounds, around the core. In the core-shell type graft copolymer, the content of the polymer component in the core is preferably 40% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and even more preferably 80% by mass or more.

[0228] Furthermore, in the shell of the core-shell graft copolymer, the total content of (meth)acrylic acid compounds (especially (meth)acrylates) and aromatic vinyl compounds is preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, and even more preferably 70% by mass or more. The shell can be made alone from either the (meth)acrylic acid compound or the aromatic vinyl compound, or they can be used together.

[0229] Preferred examples of core-shell elastomers include: methyl methacrylate-butadiene-styrene copolymer (MBS), methyl methacrylate-acrylonitrile-butadiene-styrene copolymer (MABS), methyl methacrylate-butadiene copolymer (MB), methyl methacrylate-acrylic rubber copolymer (MA), methyl methacrylate-acrylic rubber-styrene copolymer (MAS), methyl methacrylate-acrylic / butadiene rubber copolymer, methyl methacrylate-acrylic / butadiene rubber-styrene copolymer, methyl methacrylate-(acrylic / silicone composite rubber) copolymer, etc.

[0230] Commercially available core-shell graft copolymers include, for example: "PARALOID EXL2602", "PARALOID EXL2603", "PARALOID EXL2690", "PARALOID EXL2691J", "PARALOID EXL2650J", "PARALOID EXL2655", "PARALOID EXL2311", "PARALOID EXL2313", "PARALOID EXL2315", "PARALOID KM330", "PARALOID KM336P", and "PARALOID KCZ201" manufactured by Dow Chemical Japan; "METABLEN C-223A", "METABLEN E-901", "METABLEN S-2001", "METABLEN W-450A", and "METABLEN SRK-200" manufactured by Mitsubishi Chemical Corporation; and "KANE ACE M-210" and "KANE..." manufactured by KANEKA CORPORATION. ACEM-511", "KANE ACE M-600", "KANE ACE M-400", "KANE ACE M-580", "KANE ACE M-590", "KANE ACE M-711", "KANE ACE MR-01", "KANE ACE M-300", etc.

[0231] These impact modifiers, such as core-shell graft copolymers, can be used alone or in combination with two or more.

[0232] In each surface of the film (i.e., each surface layer (A)), the content of the impact modifier is preferably 30% by mass or less. By setting it to 30% by mass or less, an effect consistent with the content can be achieved, and furthermore, it is possible to prevent a decrease in various physical properties of the film, such as mechanical strength. In addition, the content of the impact modifier is preferably 1% by mass or more. By making the content of the impact modifier 1% by mass or more, it is easier to reduce the surface hardness and improve stress relaxation characteristics, etc.

[0233] The content of the impact resistance modifier is more preferably 2.5% by mass or more, further preferably 5% by mass or more, and even more preferably 7% by mass or more. Additionally, it is more preferably 20% by mass or less, further preferably 16% by mass or less, and even more preferably 12% by mass or less.

[0234] The impact resistance modifier is preferably absent in the center of the film thickness direction (i.e., the intermediate layer (B)), and even if it is present, it is present in a smaller amount than that on the film surface (i.e., the surface layer (A)). By ensuring that the intermediate layer (B) is free of the impact resistance modifier, and even if it is present, it is present in a small amount, the mechanical strength of the film is easily improved.

[0235] The content of the impact modifier in the intermediate layer (B) should preferably be less than the content of the impact modifier in each surface layer (A) based on the mass of each layer, preferably less than 4% by mass, more preferably less than 2% by mass, further preferably less than 1% by mass, even more preferably less than 0.5% by mass, and most preferably 0% by mass.

[0236] Furthermore, the content of the impact resistance modifier in this film (i.e., the film as a whole) is preferably 15% by mass or less, more preferably 10% by mass or less, even more preferably 8% by mass or less, and even more preferably 5% by mass or less. Additionally, the content of the impact resistance modifier in the film as a whole is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, and even more preferably 1.5% by mass or more.

[0237] [Particles]

[0238] This film may also contain particles. By containing particles, this film can acquire properties such as slip resistance and improve its operability. The particles are not particularly limited, and examples include: inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, alumina, and titanium dioxide; cross-linked polymers such as cross-linked silicone resin particles, cross-linked acrylic resin particles, cross-linked styrene-acrylic resin particles, and cross-linked polyester particles; and organic particles such as calcium oxalate and ion exchange resins. Among these, silica and alumina are preferred, and silica is more preferred.

[0239] Considering both the transparency and operability of the film, the average particle size is typically between 0.05 μm and 10 μm, preferably between 0.1 μm and 6 μm, more preferably between 0.3 μm and 5 μm, and even more preferably between 0.6 μm and 4.5 μm. It should be noted that the average particle size is the particle size (d50) representing 50% of the cumulative volume fraction in the equivalent spherical distribution, as measured using a centrifugal sedimentation particle size distribution measuring device.

[0240] The particles may be contained in the entire film, but are preferably contained in at least one surface of the film. Therefore, in the above multilayer structure, it is sufficient for at least one surface layer (A) to contain particles, and when there are surface layers (A) on both sides of the film, it is more preferable for both surface layers (A) to contain particles.

[0241] The particle content is not particularly limited, but is typically less than 5% by mass, preferably 0.0003% by mass or more and 3% by mass or less, more preferably 0.001% by mass or more and 2.5% by mass or less, and even more preferably 0.01% by mass or more and 1% by mass or less. When particles are absent or the particle content is low, a film with excellent transparency will be formed. On the other hand, if particles are present within the above range, slipability and operability can be improved. Furthermore, even when particles are present, if the particle content is less than 5% by mass, the transparency of the film can be sufficiently ensured. It should be noted that the particle content only needs to reach the above range in a region extending at least 1 μm from the film surface to a depth in the thickness direction. In the case of a multilayer film structure, the particle content in the surface layer (A) only needs to reach the above range; in the case of a single-layer structure, the content relative to the entire film only needs to reach the above range.

[0242] Furthermore, when the film has a multilayer structure, the particle content relative to the overall film is preferably 0.0001% by mass or more and 2% by mass or less, more preferably 0.0005% by mass or more and 1.5% by mass or less, even more preferably 0.001% by mass or more and 1% by mass or less, and even more preferably 0.005% by mass or more and 0.7% by mass or less.

[0243] [Other ingredients]

[0244] In addition to the particles mentioned above, this film may contain, as needed, existing and known antioxidants, ultraviolet absorbers, antistatic agents, heat stabilizers, lubricants, dyes, pigments, and other colorants.

[0245] [Hardness other than surface hardness]

[0246] The hardness measured at the center of the film thickness direction using a nanoindenter at 23±5°C is preferably higher than the hardness measured at 23±5°C on one surface of the film. This increased hardness at the center imparts a certain degree of rigidity to the substrate and facilitates proper wafer retention when attached as a protective sheet.

[0247] From the same point of view, the hardness of the central portion measured by a nanoindenter at 23±5°C is preferably higher than the hardness of either of the two surfaces of the film measured by a nanoindenter at 23±5°C.

[0248] It should be noted that, regarding the hardness of the central portion in the thickness direction, it is advisable to use known methods to cut the film along the surface direction to expose the central portion in the thickness direction, and to create a smooth surface by using a cutting section such as a diamond cutter as needed, and then measure the hardness of the central portion in the thickness direction using a nanoindenter.

[0249] The film also preferably has the aforementioned hardness gradient that increases from one surface of the film toward the center in the thickness direction. That is, preferably, from one surface of the film toward the center, at least a region with low hardness (first region) and a region with higher hardness than the first region (second region) are provided sequentially.

[0250] Furthermore, the aforementioned hardness gradient preferably increases from one surface toward the center and then decreases toward the other surface. That is, it is preferable to sequentially provide a low-hardness region (first region), a high-hardness region (second region), and a low-hardness region (first region) from one surface to the other.

[0251] As described above, this film is preferably a multilayer film. In the case of a multilayer film, it is preferable to have the aforementioned hardness gradient by having a surface layer (A) and an intermediate layer (B), as described above.

[0252] Furthermore, even a single-layer film can be adjusted to have a hardness gradient. In a single-layer film, this can be achieved by gradually changing the fit from the surface towards the center in the thickness direction. By making the fit gradually change from the surface towards the center in the thickness direction, the hardness at each location in the thickness direction can also gradually change.

[0253] It should be noted that, regarding the hardness at various locations in the thickness direction, it is advisable to use known methods to cut the film along the surface direction to expose various locations in the thickness direction, and to use a diamond cutter or other cutting cross-section to create a smooth surface, and then use a nanoindenter to measure the hardness at various locations in the thickness direction.

[0254] To achieve a gradual change in the blending, specifically, the film should contain two or more polyesters, with the content of at least one polyester gradually decreasing from the surface towards the center, while the content of at least another polyester gradually increases from the surface towards the center. In this way, by gradually changing the blending, the blending between the center and the surface in the thickness direction can be altered without the need for interlayer separation.

[0255] More specifically, when the proportion (molar percentage) of dicarboxylic acid components with 4 to 10 carbon atoms (excluding terephthalic acid) in all polyester components at each position in the thickness direction is set as (C1); and when the proportion (molar percentage) of diol components (excluding ethylene glycol) in all polyester components at each position in the thickness direction is set as (C4), the (C1) + (C4) ratio should gradually decrease from each surface toward the center.

[0256] Similarly, when the proportion of polyarylate (c) and dicarboxylic acid components (X2) with 4 to 10 carbon atoms (excluding terephthalic acid) in all polyesters contained at each position in the thickness direction is set as (C2), and the proportion of polyarylate (c) and diol components (X2) with excluding ethylene glycol in all polyesters contained at each position in the thickness direction is set as (C5), the ratio of (C2) + (C5) should gradually decrease from each surface toward the center.

[0257] [Physical properties of this film]

[0258] (Glass transition temperature)

[0259] The glass transition temperature (Tg) of this thin film is not particularly limited, but is preferably 30°C or higher. By setting the Tg to 30°C or higher, the heat resistance of this thin film becomes good. A Tg of 40°C or higher is more preferred, 50°C or higher is even more preferred, and 60°C or higher is still more preferred. Furthermore, from the viewpoint of reducing hardness and improving stress relaxation characteristics, a Tg of a certain value or lower is preferable, preferably 80°C or lower, more preferably 75°C or lower, even more preferably 73°C or lower, and still more preferably 71°C or lower.

[0260] (Elongation at break)

[0261] The preferred tensile elongation at break of this film is 160% or more at 25°C. A tensile elongation at break of 160% or more at 25°C facilitates the maintenance of high elongation at room temperature, making it suitable for the stretching processes described later. Furthermore, it ensures the flexibility of the film and facilitates the reduction of surface hardness.

[0262] In order to ensure flexibility and excellent elongation at room temperature, the tensile elongation at break of this film at 25°C is more preferably 170% or more, further preferably 180% or more, and even more preferably 190% or more.

[0263] In addition, the above-mentioned tensile elongation at break is not particularly limited, but in order to easily impart a certain mechanical strength to the film, it is, for example, 500% or less, preferably 400% or less, and more preferably 300% or less.

[0264] (Tensile fracture stress)

[0265] The tensile breaking stress of this film is preferably 50 MPa or more at 25°C. By setting the tensile breaking stress to 50 MPa or more, it is easy to impart a certain mechanical strength to this film. From this point of view, the tensile breaking stress at 25°C is more preferably 70 MPa or more, further preferably 80 MPa or more, and even more preferably 100 MPa or more.

[0266] From the viewpoint of easily improving the tensile elongation at break, the tensile stress at 25°C is, for example, 500 MPa or less, preferably 400 MPa or less, more preferably 300 MPa or less, and even more preferably 200 MPa or less.

[0267] (Tensile stress at 5% or 100% elongation)

[0268] This film is not particularly limited. For example, the tensile stress at 5% elongation is preferably 10 MPa or more and 150 MPa or less, more preferably 20 MPa or more and 100 MPa or less, even more preferably 40 MPa or more and 90 MPa or less, and even more preferably 50 MPa or more and 85 MPa or less.

[0269] In addition, the film is not particularly limited, but the tensile stress at 100% elongation is preferably 20 MPa or more and 200 MPa or less, more preferably 35 MPa or more and 180 MPa or less, even more preferably 50 MPa or more and 160 MPa or less, and even more preferably 90 MPa or more and 150 MPa or less.

[0270] It should be noted that the tensile elongation at break, tensile stress at break, and tensile stress at 5% or 100% elongation of the film should be measured on MD and TD and their average values ​​should be calculated. The measurement methods are detailed in the examples.

[0271] <Method for manufacturing this thin film>

[0272] As an example of the manufacturing method of this film, the manufacturing method when this film is a biaxially stretched film will be described. However, the manufacturing method described here is not the only one.

[0273] When the film is a biaxially stretched polyester film, it is advisable to first manufacture an unstretched sheet and then stretch it in two directions to obtain a biaxially stretched polyester film.

[0274] The unstretched sheet is preferably obtained as follows: polyester, along with impact modifiers, granules, and other additives as needed, is fed into an extruder and appropriately mixed. The mixture is then extruded from a die using the extruder as a molten sheet, and cooled and solidified using a cooling roller. In this case, to improve the flatness of the sheet, it is preferable to improve the adhesion between the sheet and the cooling roller, and electrostatic adhesion and / or liquid coating adhesion methods are preferred. Furthermore, the extruder should preferably mix the polyesters in a manner that ensures their compatibility; specifically, mixing should preferably be carried out at 260–300°C, preferably 265–295°C, and more preferably 270–290°C.

[0275] Next, the unoriented sheet is stretched in one direction using a stretching machine, either a roller or a tenter frame. The stretching temperature is typically 25–120°C, preferably 35–100°C, and the stretching ratio is typically 2.5–7 times, preferably 2.8–6 times.

[0276] Next, stretching is performed in a direction orthogonal to the stretching direction of the first stage. At this time, the stretching temperature is usually 50 to 140°C, and the stretching ratio is usually 3.0 to 7 times, preferably 3.5 to 6 times.

[0277] It should be noted that, in the above stretching process, a method of stretching in one direction in two or more stages can also be used.

[0278] After stretching, the film is then heat-cured at a temperature of, for example, 130–270°C, preferably 165–260°C, and more preferably 200–240°C, under tension or with a relaxation of up to 30%, to obtain the biaxially oriented film. This heat-curing treatment improves the film's flexibility and heat resistance. Furthermore, it facilitates the adjustment of the surface hardness. It should be noted that the heat-curing treatment is preferably performed at a temperature 5–70°C below the melting point of the polyester.

[0279] In addition, when the film is a multilayer polyester, it is sufficient to co-extrude the polyester layers that make up each layer to form an integral film, and then perform stretching and heat-fixing treatment as described above.

[0280] It should be noted that whether stretching has been performed can be confirmed by measuring the orientation direction, degree of orientation, and retardation of the molecular chains in the film.

[0281] <Laminated Thin Films>

[0282] This film can be laminated with other layers on one or both surfaces of the film, and used as a laminated film. One embodiment of the laminated film of the present invention has the aforementioned film and a functional layer disposed on one or another surface of the film.

[0283] (Resin layer)

[0284] As a functional layer, there are no particular limitations, and a resin layer is an example. In this film, one or more resin layers may be provided. Preferably, an easy-bonding layer and an antistatic layer are examples of resin layers. The easy-bonding layer is a layer provided to allow other layers or films to adhere to this film; there are no particular limitations, but it is preferably formed from adhesive resins such as polyurethane-based resins, vinyl-based resins, polyamide-based resins, polyester-based resins, acrylic resins, and polyvinyl acetal-based resins. Various crosslinking agents, particles, and other additives should be appropriately added to the resin of the easy-bonding layer.

[0285] The thickness of the easy-to-adhere layer is not particularly limited, for example, it is 0.001 μm or more and 3 μm or less, preferably 0.005 μm or more and 1 μm or less, more preferably 0.01 μm or more and 0.5 μm or less, and even more preferably 0.03 μm or more and 0.3 μm or less.

[0286] Furthermore, when an easy-to-adhere layer is provided in the laminated film, the easy-to-adhere layer is preferably provided on one surface of the film where the hardness, as measured by a nanoindenter at 23°C, reaches a certain value or below. The side with the easy-to-adhere layer is typically provided with an adhesive layer (described later) and attached to the substrate such as a wafer or chip. Therefore, by reducing the hardness of the surface where the easy-to-adhere layer is provided as described above, damage to the substrate such as a wafer or chip can be effectively suppressed when it is attached to the substrate.

[0287] The antistatic layer is a layer containing an antistatic agent. There are no particular limitations on the antistatic agent; existing and known antistatic agents can be used. A polymeric antistatic agent is preferred. Examples of polymeric antistatic agents include compounds with ammonium groups, polyether compounds, compounds with sulfonic acid groups, betaine compounds, and conductive polymers. Among these, compounds with ammonium groups and compounds with sulfonic acid groups are preferred, and compounds with ammonium groups are more preferred. Furthermore, among compounds with ammonium groups, compounds with pyrrolidine rings are preferred from the perspective of excellent antistatic properties and heat stability. Compounds with pyrrolidine rings are preferably compounds obtained by cyclizing diallylamine derivatives using a free radical polymerization catalyst. Alternatively, compounds having carbon-carbon unsaturated bonds that are polymerizable with diallylamine derivatives can also be used as copolymer components.

[0288] On the other hand, from the perspective of excellent antistatic properties, conductive polymers are preferred. Examples of conductive polymers include polythiophene-based, polyaniline-based, polypyrrole-based, and polyacetylene-based polymers. Among them, polythiophene-based polymers, in which poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid are used in combination, are suitable for example.

[0289] In addition to antistatic agents, the antistatic layer should also contain adhesive resins, as described above. Furthermore, various crosslinking agents, particles, and other additives should be appropriately incorporated into the adhesive resin.

[0290] The thickness of the antistatic layer is not particularly limited, for example, it is 0.001 μm or more and 3 μm or less, preferably 0.005 μm or more and 1 μm or less, more preferably 0.01 μm or more and 0.5 μm or less, and even more preferably 0.02 μm or more and 0.2 μm or less.

[0291] The surface resistivity of the laminated film with the antistatic layer preferably has a surface resistivity of 1×10⁻⁶ on the side where the antistatic layer is located. 12 Below Ω / □. By keeping the inherent surface resistivity below a certain value as described above, the laminated thin film can prevent charging and prevent damage to the circuits formed on the wafer due to electrostatic and other electrical effects.

[0292] The aforementioned surface resistivity is more preferably 1×10⁻⁶. 11 Ω / □ or less, further preferably 1×10 10 Below Ω / □. The inherent surface resistivity is not particularly limited; for example, it can be 1 × 10⁻⁶. 4 Ω / □ or higher can also be 1×10 5 Ω / □ and above.

[0293] The laminated film is also preferably provided with an easy-to-adhere layer on one surface and an antistatic layer on the other surface. Furthermore, when the film has functional layers such as an antistatic layer or an easy-to-adhere layer, it is preferable to stretch the film together with the antistatic layer or easy-to-adhere layer while it is laminated. This allows the functional layer to be easily thinned through a simple process.

[0294] (Adhesive layer)

[0295] Furthermore, the laminated film preferably contains an adhesive layer as the aforementioned resin layer. The laminated film becomes an adhesive tape by having an adhesive layer. Because of the adhesive layer, the laminated film can be bonded to wafers, etc., and is suitable as a protective tape. The adhesive layer is a pressure-sensitive adhesive layer, preferably formed from a known adhesive. The adhesive is not particularly limited; materials known to date, such as acrylic, silicone, urethane, and polyester, can be used. Alternatively, the adhesive layer can be UV-curable, cured by UV irradiation, thereby reducing the adhesion to the adhered object. If the adhesive layer is UV-curable, the peelability when peeling off the adhered object, such as a wafer or chip, is improved by irradiating it with UV light before peeling it off from the adhesive layer.

[0296] The adhesive layer is preferably disposed on any surface of the film, but preferably on one surface of the film where the hardness, as measured by a nanoindenter at 23°C, is below the aforementioned certain value. Furthermore, when an easy-to-adhere layer is disposed on a laminated film, the adhesive layer is preferably laminated on top of the easy-to-adhere layer. By laminating the adhesive layer on the easy-to-adhere layer, the adhesive layer will be held in place with high holding force within the film.

[0297] The laminated film with an adhesive layer is attached to the substrate such as a wafer via the adhesive layer. By reducing the hardness of the surface of the film on the side where the adhesive layer is provided, as described above, the film can be used to appropriately relax stress when attached to the wafer, thereby effectively suppressing the breakage of the wafer or chip.

[0298] <Instructions for using this film>

[0299] This film is used in semiconductor manufacturing processes. It is preferably used, for example, as a protective tape attached to a wafer to protect it or as part of a chip monolithically formed from a wafer.

[0300] Typically, semiconductor manufacturing processes include: a back-side grinding process, in which a predetermined circuit pattern is formed on the surface of a semiconductor wafer, and then the opposite side of the semiconductor wafer is ground to adjust the wafer thickness; a dicing process, in which the semiconductor wafer is separated into individual chips; and a pick-up process, in which the separated chips are picked up. This thin film is preferably used as a protective tape substrate for bonding to the circuit surface of the semiconductor wafer in any of these processes, and more preferably as a back-side grinding tape used in the back-side grinding process.

[0301] Because one surface of this film has low hardness, by attaching it to the wafer with one surface side, it can properly relax the stresses such as shear forces acting on the wafer and chip during wafer grinding, effectively preventing the wafer and chip from breaking.

[0302] Alternatively, the dicing process can be performed using a blade to cut the wafer, or it can be done through stealth dicing. Stealth dicing is performed as follows: a modified layer is formed using a laser as the starting point for dicing; then, external stress is applied to the wafer, monolithizing the wafer into individual chips starting from the modified layer. It should be noted that in stealth dicing, external stress is preferably applied through a so-called extension process, such as stretching the adhesive tape attached to the wafer along its outer periphery.

[0303] Furthermore, the aforementioned dicing process is typically performed after the back-side grinding process, but it is preferably performed using the so-called pre-dicing (DBG) method. The pre-dicing method is as follows: a groove is formed on the surface side of the wafer using a dicing blade, and then the back side of the wafer is ground to reach the groove, thereby separating the wafer into multiple chips starting from the groove.

[0304] Alternatively, the pre-cutting method can also be performed using laser-irradiated stealth dicing before grinding (SDBG). SDBG is a method in which a modified layer is formed on the wafer by laser irradiation, and then the wafer is separated into individual chips starting from the modified layer by subsequent back-side grinding.

[0305] This film is preferably used as a substrate for back-side grinding as described above, and more preferably as a substrate for a back-side grinding belt used in a pre-dicing process. In the pre-dicing process, since the chip monolithization and grinding are performed simultaneously, the monolithized chip is prone to cracking during grinding. However, as described above, this film has low surface hardness and excellent stress relaxation characteristics, so even when used in the pre-dicing process, it can properly prevent wafer and chip breakage.

[0306] <<Explanation of the statement>>

[0307] In this invention, even when referred to as a "film", it also includes a "sheet" and even when referred to as a "sheet", it also includes a "film".

[0308] In this invention, when referred to as "X to Y" (where X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", and also includes the meaning of "preferably greater than X" or "preferably less than Y".

[0309] In addition, when it is recorded as "X or above" (where X is any number), unless otherwise specified, it includes the meaning of "preferably greater than X". When it is recorded as "Y or below" (where Y is any number), unless otherwise specified, it also includes the meaning of "preferably less than Y".

[0310] Example

[0311] Examples and comparative examples will be shown below, but the invention is not limited thereto.

[0312] The evaluation and measurement methods are described below.

[0313] [Hardness (Nano Indenter)]

[0314] The polyester films obtained in the various examples, comparative examples, and reference examples were cut into 20mm × 20mm squares, and the resulting test pieces were attached to a glass substrate using wood glue. For the surface layer (A) side of the test piece attached to the glass substrate, the hardness was measured at room temperature (23 ± 5°C) using a nanoindentation device, "Hysitron TI980 (manufactured by BRUKER)". Specifically, an indentation test was performed from the surface layer (A) side of the obtained test piece using a diamond Berkovich-type (triangular pyramidal) probe to obtain the displacement-load hysteresis curve. The indentation test was conducted with the maximum load set so that the probe contact depth reached approximately 1000 ± 100 nm.

[0315] The indentation test process of the nanoindenter is as follows.

[0316] (1) In order to detect the surface of the test piece, bring the probe close to the surface of the test piece until the specified load (2μN) is detected.

[0317] (2) Remove the probe from the sample until the load reaches 0 μN. At this point, if the sample surface is in contact with the probe, a negative load will be detected; if the probe is completely removed from the sample, a flat portion will appear in the load-displacement curve.

[0318] (3) The probe is pressed into and pulled out of the sample.

[0319] In each embodiment, comparative example, and reference example, tests were conducted with a lift height of 100 nm, a load time of 5 seconds, a hold time of 2 seconds, and an unload time of 5 seconds.

[0320] It should be noted that Lift Height refers to the probe's withdrawal distance when the load in (2) above actually reaches 0 μN. The load can also become 0 μN when the withdrawal distance reaches the value of Lift Height, but it is preferable that the load becomes 0 μN before the withdrawal distance reaches the value of Lift Height.

[0321] The displacement-load hysteresis curves obtained by the above method were numerically processed using the software accompanying the device (Triboscan 10.2.0.2) to calculate the hardness. The hardness is the average value of the hardness obtained from the test at 40 points (10 μm intervals). It should be noted that the AreaFunction required for indenter shape correction during numerical analysis was prepared using the results of fused silica measurements.

[0322] [Glass transition temperature of polyester film]

[0323] Using a differential scanning calorimeter "DSC8500" (manufactured by Perkin Elmer), according to JIS K7121:2012, the glass transition temperature was measured by heating from -30°C to 200°C at a rate of 10°C / min, cooling to 30°C at a rate of 20°C / min, and then heating back to 200°C at a rate of 10°C / min. It should be noted that the method for determining the glass transition temperature is based on the midpoint glass transition temperature (Tmg).

[0324] [Inherent surface resistivity]

[0325] (1) Less than 1×10 7 Ω / □ case

[0326] Using a low resistivity meter “Loresta GP MCP-T600” manufactured by Mitsubishi Chemical Corporation, the sample was conditioned for 30 minutes at a temperature of 23°C and a relative humidity of 50%, and the inherent surface resistivity was measured. The value after 1 minute was taken as the inherent surface resistivity.

[0327] (2) Other than the above situations

[0328] Using a high-resistivity resistivity meter "Hiresta UX MCP-HT800" manufactured by Mitsubishi Chemical Analysis Technology Co., Ltd., and a measuring electrode "UR-100", the sample was conditioned for 30 minutes at 23°C and 50%RH, and then measured under an applied voltage of 500V. The value after 1 minute was taken as the intrinsic surface resistivity. If the intrinsic surface resistivity exceeds the upper limit of the measurable range, it is recorded as unmeasurable.

[0329] [Young's modulus of polyester film]

[0330] From the polyester films obtained in the various embodiments, comparative examples, and reference examples, a sample film with a width of 20 mm and a length of 170 mm was taken. The Young's modulus was measured using an Autograph AGX-V (manufactured by Shimadzu Corporation) in an indoor environment conditioned at 23°C and 50% RH. Tensile measurements were performed along the length direction (MD) and width direction (TD) of the sample film under conditions of a chuck distance of 120 mm and a tensile speed of 10 mm / min. It should be noted that the following formula was used in the calculation of the Young's modulus.

[0331] E=Δσ / Δε

[0332] (In the formula, E is Young's modulus (GPa), Δσ is the stress difference between two points on the line based on the original average cross-sectional area (GPa), and Δε is the strain difference between two points of the same length / initial length)

[0333] Five measurements were taken along the length (MD) and width (TD) directions of the film, and the average values ​​were calculated as the MD Young's modulus and TD Young's modulus, respectively. The average of the MD Young's modulus and TD Young's modulus was taken as the Young's modulus of the polyester film.

[0334] [Tension test]

[0335] (1) Tensile fracture stress

[0336] Using a tensile testing machine (manufactured by INTESCO Co., Ltd., INTESCO Model 2001), in an indoor environment regulated to 25°C and 50%RH, a 15mm wide polyester film (sample) was placed on the testing machine with a chuck spacing of 50mm, and stretched at a strain rate of 200mm / min. The tensile fracture stress in the length direction (MD) and width direction (TD) of the film was then calculated using the following formula.

[0337] Tensile fracture stress (MPa) = F / A

[0338] In the formula, F is the load at fracture (N), and A is the original cross-sectional area of ​​the test piece (mm²). 2 ).

[0339] Five points were measured along the length (MD) and width (TD) of the film, and the average values ​​were calculated as the MD tensile breaking stress and TD tensile breaking stress, respectively. The average value of the MD tensile breaking stress and TD tensile breaking stress was taken as the tensile breaking stress of the polyester film.

[0340] (2) Elongation at break

[0341] For the polyester films (samples) obtained in the Examples, Comparative Examples, and Reference Examples, the same test as the tensile breaking stress was performed, and the tensile breaking elongation in the length direction (MD) and width direction (TD) of the film was determined by the following formula.

[0342] Elongation at break (%) = 100 × (L - L0) / L0

[0343] In the formula, L is the distance between punctuation marks at the time of breakage (mm), and L0 is the original distance between punctuation marks (mm).

[0344] Five measurements were taken along the length (MD) and width (TD) of the film, and the average values ​​were calculated as the MD tensile elongation at break and the TD tensile elongation at break. The average of the MD tensile elongation at break and the TD tensile elongation at break was taken as the tensile elongation at break of the polyester film.

[0345] (3) Tensile stress at 5% and 100% elongation

[0346] For the polyester films (samples) obtained in the Examples, Comparative Examples, and Reference Examples, the same test as the tensile breaking stress was performed, and the tensile stress at 5% elongation in both the length direction (MD) and width direction (TD) of the film was determined by the following formula.

[0347] Tensile stress at 5% elongation (MPa) = F5 / A

[0348] In the formula, F5 is the load (N) at 5% elongation, and A is the original cross-sectional area of ​​the test piece (mm²). 2 ).

[0349] Five points were measured along the length (MD) and width (TD) of the film, and the average values ​​were calculated as the tensile stress at 5% elongation of MD and 5% elongation of TD. The average of the tensile stress at 5% elongation of MD and TD was taken as the tensile stress at 5% elongation of the polyester film.

[0350] In addition, the load (N) at 100% elongation was also measured, and the tensile stress at 100% elongation was calculated in the same way as the tensile stress at 5% elongation.

[0351] (raw material)

[0352] The following raw materials were used in the examples, comparative examples and reference examples.

[0353] • Copolyester (1): Thermoplastic polyester

[0354] Prepare a copolyester (1) containing terephthalic acid and adipic acid (6 carbon atoms) as dicarboxylic acid components, the content of terephthalic acid is 85 mol%, the content of adipic acid is 15 mol%, and it contains 45 mol% 1,4-butanediol and 55 mol% 1,6-hexanediol as diol components.

[0355] • Copolyester (2): Thermoplastic polyester

[0356] Prepare a copolyester (2) (intrinsic viscosity (IV) 0.70 dl / g), which contains terephthalic acid and isophthalic acid as dicarboxylic acid components, the content of terephthalic acid is 78 mol%, the content of isophthalic acid is 22 mol%, and as diol components, ethylene glycol is 98 mol% and diethylene glycol is 2 mol%.

[0357] • Copolyester (3): Thermoplastic polyester

[0358] Prepare a copolyester (3) whose dicarboxylic acid component is composed of terephthalic acid, ethylene glycol is 68 mol%, and 1,4-cyclohexanediethanol (CHDM) is 32 mol%.

[0359] • Polyarylate

[0360] Prepare U-POLYMER (registered trademark) U-100 (manufactured by UNITIKA LTD., dicarboxylic acid composition: terephthalic acid / isophthalic acid = 50 / 50 mol%, bisphenol composition: bisphenol A = 100 mol%, Tg = 210℃).

[0361] • Homopolymer polyester (1): thermoplastic polyester

[0362] Prepare a homopolymer polyester (1) containing particles (i.e., homopolymer PET), which is a polyester whose dicarboxylic acid component is composed of terephthalic acid and whose diol component is 98 mol% ethylene glycol and 2 mol% diethylene glycol, has an intrinsic viscosity (IV) of 0.62 dl / g, and contains 0.55 wt% silica particles with an average particle size of 3 μm.

[0363] • Homopolymer polyester (2): thermoplastic polyester

[0364] Prepare a homopolymer (2), which is a polyester whose dicarboxylic acid component is composed of terephthalic acid and whose diol component is 98 mol% ethylene glycol and 2 mol% diethylene glycol, with an intrinsic viscosity (IV) of 0.645 dl / g.

[0365] • Homopolymer polyester (3): thermoplastic polyester

[0366] Prepare a homopolymer polyester (3) containing particles (homogeneous PET), which is a polyester whose dicarboxylic acid component is composed of terephthalic acid and whose diol component is 98 mol% ethylene glycol and 2 mol% diethylene glycol, with an intrinsic viscosity (IV) of 0.590 dl / g, and contains 0.7 wt% silica particles with an average particle size of 3 μm.

[0367] • Homopolymer polyester (4): thermoplastic polyester

[0368] Prepare a homopolymer (4), which is a polyester whose dicarboxylic acid component is composed of terephthalic acid and whose diol component is 98 mol% ethylene glycol and 2 mol% diethylene glycol, with an intrinsic viscosity (IV) of 0.7 dl / g.

[0369] • Homopolymer polyester (5): thermoplastic polyester

[0370] Prepare a homopolymer polyester (5) containing particles (homogeneous PET), which is a polyester whose dicarboxylic acid component is composed of terephthalic acid and whose diol component is 98 mol% ethylene glycol and 2 mol% diethylene glycol, with an intrinsic viscosity (IV) of 0.65 dl / g, and contains 0.6 wt% silica particles with an average particle size of 3 μm.

[0371] • Homopolymer polyester (6): thermoplastic polyester

[0372] Prepare a homopolymer (4), which is a polyester whose dicarboxylic acid component is composed of terephthalic acid and whose diol component is 98 mol% ethylene glycol and 2 mol% diethylene glycol, with an intrinsic viscosity (IV) of 0.580 dl / g.

[0373] • Impact resistance modifier

[0374] Maleic anhydride modified hydrogenated styrene thermoplastic elastomer (SEBS), manufactured by Asahi Kasei Chemicals, "Tuftec M1943".

[0375] (Example 1)

[0376] As shown in Table 1, as the raw material for the surface layer (A), 38 parts by weight of copolyester (1), 42 parts by weight of polyarylate, 10 parts by weight of homopolymer (1), and 10 parts by weight of impact modifier are dry-mixed. As the raw material for the intermediate layer (B), 10 parts by weight of copolyester (2) and 90 parts by weight of homopolymer (2) are dry-mixed.

[0377] The mixed raw materials of the surface layer (A) and the intermediate layer (B) were fed into different twin-screw extruders and mixed at 285°C. They were then co-extruded at 285°C and cooled and solidified on cooling rollers set at 25°C using an electrostatic sealing method, thereby obtaining two types of three-layer (surface layer (A) / intermediate layer (B) / surface layer (A)) unstretched films.

[0378] Next, the obtained unstretched film was stretched to 3 times its original thickness along the longitudinal direction (MD) at 65°C using a roller stretcher. Then, an easy-to-adhesive layer coating liquid (solid content concentration: 9.0% by mass) was applied to one side of the polyester film via online coating, i.e., the coating liquid was applied to one side of the polyester film in such a way that the thickness after drying and stretching is as shown in Table 1, forming an easy-to-adhesive layer. Next, it was fed into a tenter frame and stretched to 3.1 times its original thickness along the transverse direction (TD) at 100°C. Then, a heat-setting treatment was performed at a heat-setting temperature of 210°C for 7 seconds, followed by a cooling treatment at 140°C with 2.5% relaxation along the transverse direction (TD), to obtain a polyester film with a thickness of 80 μm (surface layer (A): 8 μm, intermediate layer (B): 64 μm).

[0379] (Formulation of coating liquid for easy-to-adhesive layers)

[0380] Aqueous dispersion of polyester resin formed from terephthalic acid / isophthalic acid / sodium sulfoisophthalate / ethylene glycol / diethylene glycol / triethylene glycol = 61 / 32 / 7 / 44 / 43 / 13 (mol%): 20 parts by weight

[0381] Aqueous dispersion of polyester polyurethane resin formed from isophorone diisocyanate units / terephthalic acid units / isophthalic acid units / ethylene glycol units / diethylene glycol units / dimethylolpropionic acid units = 12 / 19 / 18 / 21 / 25 / 5 (mol%): 65 parts by weight

[0382] Hexamethoxymethyl melamine: 10 parts by weight

[0383] Colloidal silica with a particle size of 50-80 nm: 5 parts by weight

[0384] 0.3 parts by weight of an acetylene-based nonionic surfactant with an HLB of 8.0 and a side chain containing polyethylene oxide:

[0385] *It should be noted that the above figures are based on the mass fraction of solid components.

[0386] (Example 2)

[0387] After applying the coating liquid to the easy-to-adhere layer and before lateral stretching, an antistatic coating liquid (1) with the following formulation (solid component concentration: 3.3% by mass) is further applied to the other side of the polyester film. That is, the coating liquid is applied to the other side of the polyester film in such a way that the thickness after drying and stretching is as shown in Table 1 to form the antistatic layer (1). Otherwise, it is carried out in the same manner as in Example 1.

[0388] (Formulation of antistatic coating liquid (1))

[0389] A polymer with a pyrrolidine ring on the main chain, obtained by polymerization of diallyl dimethylammonium chloride, dimethacrylamide, and N-hydroxymethylacrylamide in a ratio of 90 / 5 / 5 (mol%). Number average molecular weight approximately 30,000: 40 parts by mass.

[0390] An aqueous dispersion of acrylic resin formed from ethyl acrylate / methyl methacrylate = 36 / 64 (mol%): 37 parts by weight

[0391] AMIDIR MA-S (manufactured by DIC Corporation), used as a melamine crosslinking agent: 20 parts by weight

[0392] EPOCROS WS-500 (manufactured by Nippon Shokubai Co., Ltd.), a polymer containing oxazoline groups: 3 parts by weight

[0393] 2-Amino-2-methylpropanol hydrochloride: 1 part by weight

[0394] *It should be noted that the above figures are based on the mass fraction of solid components.

[0395] (Example 3)

[0396] After applying the coating liquid to the easy-to-adhere layer and before lateral stretching, an antistatic coating liquid (2) with the following combination (solid component concentration: 2.8% by mass) is further applied to the other side of the polyester film. That is, the coating liquid is applied to the other side of the polyester film in such a way that the thickness after drying and stretching is as shown in Table 1 to form the antistatic layer (2). Otherwise, it is carried out in the same way as in Example 1.

[0397] (Formulation of antistatic coating liquid (2))

[0398] The conductive agent "Orgacon ICP1010" (manufactured by Agfa-Gevaert NV), whose main components are polyvinyl dioxythiophene and polystyrene sulfonic acid, was neutralized with concentrated ammonia water to bring the pH to 9. (10 parts by weight)

[0399] When a polyester polyol comprising 282 parts by weight of terephthalic acid, 282 parts by weight of isophthalic acid, 62 parts by weight of ethylene glycol, and 250 parts by weight of neopentyl glycol is designated as (C1a), a polyester polyurethane comprising 876 parts by weight of (C1a), 244 parts by weight of toluene diisocyanate, 81 parts by weight of ethylene glycol, and 67 parts by weight of dimethylolpropionic acid is neutralized with ammonia and then dispersed in water to obtain a substance: 49 parts by weight

[0400] The compound obtained by adding an average of 4 molecules of polyethylene oxide to a polyglycerol backbone with an average n=2 in the following formula.

[0401] [Chemical Formula 1]

[0402]

[0403] Colloidal silica with a particle size of 50-80nm: 1 part by weight

[0404] In the following formula, m+n averages 10, and the structure is a nonionic surfactant with polyethylene oxide in the side chain.

[0405] [Chemical Formula 2]

[0406]

[0407] *It should be noted that the above figures are based on the mass fraction of solid components.

[0408] (Example 4)

[0409] As shown in Table 1, the raw material for the surface layer (A) was a substance obtained by dry mixing 27 parts by weight of copolyester (1), 10 parts by weight of homopolymer (1), 53 parts by weight of homopolymer (2), and 10 parts by weight of impact modifier. The mixing temperature and extrusion temperature were set to 280°C, and the heat setting temperature was changed to 230°C, so that the thickness was 77 μm (7.7 μm for each surface layer (A) and 61.6 μm for the intermediate layer (B)). Otherwise, it was carried out in the same manner as in Example 1.

[0410] (Example 5)

[0411] After applying the coating liquid to the easy-to-adhere layer and before lateral stretching, the above-mentioned antistatic coating liquid (1) (solid component concentration: 3.3% by mass) is further applied to the other side of the polyester film. That is, the coating liquid is applied to the other side of the polyester film in such a way that the thickness after drying and stretching is as shown in Table 1 to form the antistatic layer (1). Otherwise, it is carried out in the same way as in Example 4.

[0412] (Example 6)

[0413] After applying the coating liquid to the easy-to-adhere layer and before lateral stretching, an antistatic coating liquid (2) with the above-mentioned combination (solid component concentration: 2.8% by mass) is further applied to the other side of the polyester film. That is, the coating liquid is applied to the other side of the polyester film in such a way that the thickness after drying and stretching is as shown in Table 1 to form the antistatic layer (2). Otherwise, it is carried out in the same way as in Example 4.

[0414] (Example 7)

[0415] The heat setting temperature was changed to 240°C, and the thickness was 73 μm (surface layer (A): 7.3 μm, intermediate layer (B): 58.4 μm). Otherwise, it was carried out in the same manner as in Example 4.

[0416] (Example 8)

[0417] In Example 8, a single-layer polyester film was prepared. As shown in Table 2, 85 parts by weight of copolyester (2), 10 parts by weight of homopolymer (4), and 5 parts by weight of homopolymer (5) were dry-blended as raw materials. The mixed raw materials were fed into a twin-screw extruder, compounded at 280°C, extruded at 280°C, and cooled and cured on a cooling roller set at 16°C using an electrostatic sealing method, thereby obtaining a single-layer unstretched film.

[0418] Next, the obtained unstretched film was stretched to 3.4 times its original thickness along the longitudinal direction (MD) at 81°C using a roller stretcher. Then, the aforementioned easy-to-adhesive layer coating liquid (solid content concentration: 9.0% by mass) was applied to one side of the polyester film via online coating, i.e., the coating liquid was applied to one side of the polyester film in such a way that the thickness after drying and stretching is as shown in Table 2, forming an easy-to-adhesive layer. Next, it was fed into a tenter frame and stretched to 3.9 times its original thickness along the transverse direction (TD) at 80°C. Then, a heat-setting treatment was performed at a heat-setting temperature of 187°C for 10 seconds, followed by a cooling treatment at 125°C with 8% relaxation along the transverse direction (TD), to obtain a polyester film with a thickness of 50 μm.

[0419] (Example 9)

[0420] As shown in Table 2, the raw materials used were a substance obtained by dry mixing 40 parts by weight of copolyester (2), 5 parts by weight of homopolymer (5), and 55 parts by weight of copolyester (3), and the heat setting temperature was changed to 169°C. Otherwise, the process was the same as in Example 8.

[0421] (Comparative Example 1)

[0422] As shown in Table 2, the material used as the raw material for the surface layer (A) is a substance obtained by dry mixing 70 parts by mass of homopolymer (2) and 30 parts by mass of homopolymer (3), and the material used as the raw material for the intermediate layer (B) is a substance obtained by dry mixing 45 parts by mass of homopolymer (2) and 55 parts by mass of homopolymer (6).

[0423] The mixed raw materials of the surface layer (A) and the intermediate layer (B) were fed into different twin-screw extruders, mixed at 290°C, co-extruded at 290°C, and cooled and solidified on cooling rollers set at 20°C using an electrostatic sealing method, thereby obtaining two kinds of three-layer (surface layer (A) / intermediate layer (B) / surface layer (A)) unstretched films.

[0424] Next, the obtained unstretched film was stretched to 3.4 times its original length along the longitudinal direction (MD) at 90°C using a roller stretcher. Then, it was fed into a tenter frame and stretched to 4.3 times its original length along the transverse direction (TD) at 145°C. Next, a heat-setting treatment was performed at 210°C for 10 seconds, followed by a cooling treatment at 135°C with 8% relaxation along the transverse direction (TD) to obtain a polyester film with a thickness of 50 μm (surface layer (A): 4.2 μm, intermediate layer (B): 41.6 μm).

[0425] (See Example 1 for reference)

[0426] As shown in Table 2, the material used as the raw material for the surface layer (A) is a substance obtained by dry mixing 50 parts by weight of copolyester (1), 10 parts by weight of homopolymer (1), and 40 parts by weight of homopolymer (2), and the material used as the raw material for the intermediate layer (B) is a substance obtained by dry mixing 50 parts by weight of copolyester (1), 10 parts by weight of homopolymer (1), and 40 parts by weight of homopolymer (2).

[0427] The mixed raw materials of the surface layer (A) and the intermediate layer (B) were fed into different twin-screw extruders and mixed at 285°C. They were then co-extruded at 285°C and cooled and solidified on cooling rollers set at 25°C using an electrostatic sealing method, thereby obtaining two types of three-layer (surface layer (A) / intermediate layer (B) / surface layer (A)) unstretched films.

[0428] Next, the obtained unstretched film was stretched to 3 times its original length along the longitudinal direction (MD) at 40°C using a roller stretcher. Then, it was fed into a tenter frame and stretched to 4.3 times its original length along the transverse direction (TD) at 100°C. Next, it underwent a heat-setting treatment at 235°C for 7 seconds, followed by a cooling treatment at 140°C with 3.4% relaxation along the transverse direction (TD), yielding a polyester film with a thickness of 50 μm (surface layer (A): 8.3 μm, intermediate layer (B): 33.4 μm).

[0429] [Table 1]

[0430]

[0431] [Table 2]

[0432]

[0433] In the above embodiments, by using specific copolyesters and adjusting the types and amounts of dicarboxylic acid and diol components, a surface hardness of less than 450 MPa, as measured by a nanoindenter at 23°C, can be achieved. Therefore, it is understood that the present invention exhibits excellent stress relaxation characteristics, which can reduce chip and wafer breakage when used in semiconductor manufacturing. Furthermore, it is understood that the present invention, being primarily composed of polyester, also has good recyclability. Additionally, it is understood that the present invention, by reducing the hardness measured by a nanoindenter at 23°C and increasing the Young's modulus, also exhibits good mechanical strength, making it suitable for semiconductor manufacturing.

[0434] Furthermore, since Examples 1-7 are multilayer films, by adjusting the dicarboxylic acid and diol components in the surface layer (A) and the intermediate layer (B), and by employing a specific combination where (A1) + (A4) is higher than (B1) + (B4), it is possible to increase Young's modulus and other properties while reducing the hardness measured by a nanoindenter at 23°C. Therefore, it can be understood that the present invention exhibits good mechanical strength and excellent stress relaxation characteristics, making it more suitable for semiconductor manufacturing.

[0435] In contrast, in Comparative Example 1, the hardness measured by a nanoindenter at 23°C was higher than 450 MPa, indicating insufficient stress relaxation characteristics. Furthermore, in Reference Example 1, although the stress relaxation characteristics were excellent, the Young's modulus could not be improved, and the mechanical strength was not considered sufficient.

Claims

1. A polyester film for semiconductor manufacturing processes, said polyester film having a thermoplastic polyester layer comprising a thermoplastic polyester. The thermoplastic polyester layer is the surface layer (A) of the polyester film. The surface layer (A) has a hardness of less than 450 MPa as measured by a nanoindenter at 23±5℃. The polyester film has a Young's modulus of 2 GPa or higher.

2. A polyester film for semiconductor manufacturing processes, wherein the hardness of one surface of the film, as measured by a nanoindenter at 23±5°C, is below 450 MPa.

3. The polyester film for semiconductor manufacturing processes according to claim 1 or 2, wherein, The polyester film has a hardness gradient that increases from one surface of the film toward the center in the thickness direction.

4. A polyester film for semiconductor manufacturing processes, comprising a copolyester formed from a copolymer of a dicarboxylic acid component and a diol component. Let (A1) be the proportion (molar percentage) of dicarboxylic acid components with 4 to 10 carbon atoms (excluding terephthalic acid) in all polyester components contained on one surface of the film. Let (A4) be the percentage (molar percentage) of diols other than ethylene glycol in the total polyester content of the surface. Let (B1) be the percentage (molar percentage) of dicarboxylic acid components (excluding terephthalic acid) with 4 to 10 carbon atoms in all polyester components contained in the center part of the film thickness direction. When the percentage (molar percentage) of diols other than ethylene glycol in the total polyester content at the center of the film thickness direction is set as (B4), (A1) + (A4) is higher than (B1) + (B4).

5. The polyester film for semiconductor manufacturing processes according to any one of claims 1, 2, and 4, wherein, The polyester film comprises a copolyester (a), which is a copolymer containing a dicarboxylic acid component of terephthalic acid and a diol component containing an aliphatic diol (Y).

6. The polyester film for semiconductor manufacturing processes according to claim 5, wherein, The copolyester (a) comprises a copolyester (a1), which is a copolymer of a dicarboxylic acid component containing terephthalic acid (X1) and a dicarboxylic acid component (X2) having 4 to 10 carbon atoms, and a diol component containing an aliphatic diol (Y).

7. The polyester film for semiconductor manufacturing processes according to claim 5, wherein, The copolyester (a) comprises a copolyester (a1-1), which is a copolymer of a dicarboxylic acid component containing terephthalic acid (X1) and a dicarboxylic acid component (X2) having 4 to 10 carbon atoms, and a diol component containing an aliphatic diol (Y2) having 4 to 8 carbon atoms.

8. The polyester film for semiconductor manufacturing processes according to any one of claims 1, 2, and 4, wherein, The polyester film is a multilayer film having the surface layer (A) and the intermediate layer (B).

9. The polyester film for semiconductor manufacturing processes according to claim 1, wherein, The surface layer (A) comprises a copolyester formed from a copolymer of dicarboxylic acid components and diol components. Let (A1) be the proportion (molar percentage) of dicarboxylic acid components with 4 to 10 carbon atoms (excluding terephthalic acid) in all polyester components of the surface layer (A). When the proportion (molar%) of diol components other than ethylene glycol in the total polyester content of the surface layer (A) is set as (A4), (A1) + (A4) is 5 mol% or more.

10. The polyester film for semiconductor manufacturing processes according to claim 8, wherein, The intermediate layer (B) comprises a copolyester formed from a copolymer of dicarboxylic acid components and diol components. Let (B1) be the percentage (molar percentage) of dicarboxylic acid components (excluding terephthalic acid) with 4 to 10 carbon atoms in all the polyester contained in the intermediate layer (B), and... When the proportion (molar percentage) of diols other than ethylene glycol in the total polyester content of the intermediate layer (B) is set as (B4), (B1) + (B4) is less than 30 mol%.

11. The polyester film for semiconductor manufacturing processes according to claim 8, wherein, The surface layer (A) comprises a copolyester formed from a copolymer of dicarboxylic acid components and diol components. The intermediate layer (B) comprises a copolyester formed from a copolymer of dicarboxylic acid components and diol components. Let (A1) be the proportion (molar percentage) of dicarboxylic acid components with 4 to 10 carbon atoms (excluding terephthalic acid) in all polyester components of the surface layer (A). Let (A4) be the percentage (molar percentage) of diol components other than ethylene glycol in the total polyester content of the surface layer (A). Let (B1) be the percentage (molar percentage) of dicarboxylic acid components (excluding terephthalic acid) with 4 to 10 carbon atoms in all the polyester contained in the intermediate layer (B), and... When the proportion (molar percentage) of diols other than ethylene glycol in the total polyester content of the intermediate layer (B) is set as (B4), (A1) + (A4) is higher than (B1) + (B4), and the difference is greater than 5 mol%.

12. The polyester film for semiconductor manufacturing processes according to claim 1, wherein, The surface layer (A) contains an impact resistance modifier.

13. The polyester film for semiconductor manufacturing processes according to claim 12, wherein, The impact resistance modifier is present in a concentration of less than 30% by mass in the surface layer (A).

14. The polyester film for semiconductor manufacturing processes according to claim 12, wherein, The impact resistance modifier is present in a concentration of less than 15% by mass in the polyester film.

15. The polyester film for semiconductor manufacturing processes according to any one of claims 1, 2, and 4, wherein, The polyester film is a stretched film.

16. The polyester film for semiconductor manufacturing processes according to any one of claims 1, 2, and 4, wherein, The polyester film is a co-extruded stretched film.

17. The polyester film for semiconductor manufacturing processes according to any one of claims 1, 2, and 4, wherein, The polyester film is used for back-side grinding or cutting.

18. A laminated thin film comprising: a polyester film for semiconductor manufacturing process according to claim 1, and at least one resin layer disposed on one or the other surface of the polyester film for semiconductor manufacturing process.

19. The laminated film according to claim 18, wherein, The resin layer includes an antistatic layer, and the surface resistivity of one side of the antistatic layer is set to 1×10⁻⁶. 12 Below Ω / □.

20. The laminated film according to claim 18, wherein, The resin layer includes an adhesive layer.

21. The laminated film according to claim 19, wherein, One surface has an easy-to-adhere layer, and the other surface has an antistatic layer.

22. A method of use in which a polyester film for semiconductor manufacturing processes according to any one of claims 1, 2 and 4, or a laminated film according to any one of claims 18 to 21, is used for back-side grinding or cutting.

Citation Information

Patent Citations

  • Carrier tape

    JP1992257444A

  • Back grinding film and method for manufacturing the same

    JP2010225675A

  • Surface protection sheet

    JP2012216619A

  • Substrate film for back-grinding tape

    JP2021146675A

  • Protective sheet for workpiece processing and manufacturing method for singulated workpiece

    JP2023094525A